Regulation of casein micelles dissociation by sodium tripolyphosphate to improve gel properties as stabilizers and protein fortifier for high-protein yogurt - Zi-Ying Zhao; Zi-Wei Liu; Bo-Kang Yu; Ying-Chao Qiu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Exploring immunomodulatory peptides derived from bovine colostrum protein based on QSAR models: preparation, identification, in vitro activity, and molecular docking analysis - Ying-Chao Qiu; Zi-Ying Zhao; Stella Zhu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Comparative structural, colloidal, and kinetic evaluation of yeast, soy, and whey proteins: uncovering the modification needs of yeast protein - Siliang Wu; Kewei Chen; Wen Li; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Enhancing bioaccessibility and interfacial functional properties of yeast protein via the strategy of two-stage ultrasound processing: insights from the Bayesian optimization, structural characterization and kinetics - Siliang Wu; Yuting Liu; Wen Li; Kewei Chen; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Microbiota–liver axis and host transcriptomic mechanisms underlying the anti-obesity effects of Bifidobacterium animalis DPU-MWFBA in early-life overfeeding - Zhongyang Gao; Baoyuan Zhao; Guangqing Mu; Hui Nie; Xiaomeng Wu (Food Microbiology, 2026)

OLFM4 mediating ischemia/reperfusion-induced kidney injury by regulating renal tubular epithelial cells ferroptosis via GPX4 - Zehao Zhang; Yaqi Wang; Zhiqiang Mu; Sheng Zhao; Tingting Zhang; Ziqi Zhang; Shiren Sun; Ming Bai (Molecular Biology Reports, 2026)

Surface-confined AlOxFy on thermal shock-generated α-Al2O3 for coke-resistant dehydrofluorination of 1,1-difluoroethane - Zhenxiang Li; Yongchao Zhao; Fengqing Hu; Zaizhe Cheng; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Ying Li; Wujian Zhang; Haodong Tang (Chemical Engineering Journal, 2026)

Highly antifouling field-effect transistor biosensors: From interface design to practical applications - Jiajun Tong; Rong Mu; Luming Zhi; Ruilian Yu; Kemin Wang; Zijun Zhao; Yiwei Liu; Taiping Qing; Xiaofeng Liu (Chemical Engineering Journal, 2026)

A double-key responsive TDNs-HC/Cas13a DNA circuit for free-amplified detection and precise imaging of miRNAs in living cell - Shixiu Xiao; Yuying Liang; Yihan Zhang; Longjin Liang; Bin Xu; Xiaomei Mu; Shulin Zhao; Jianniao Tian (Analytica Chimica Acta, 2026)

Bioluminescent enzyme immunoassay for cortisol by exploitation of single-chain variable fragment and single-chain variable fragment-nanoluciferase fusion protein - Xiping Cui; Qiyi He; Huiyi Yang; Mingxia Lin; Suqing Zhao; Yunping Mu (Analytica Chimica Acta, 2026)

Spatiotemporal predictive modeling for coastal phytoplankton based on the Tapnet model: A case study in Zhejiang, China - Yan Wei; Haibin Han; Qinglin Mu; Haodi Zhu; Yueyi Qiao; Shaojian Yang; Chaoyi Yu; Na Wei; Hanyan Luo; Luyuan Zhao; Xuping Zhuo; Yufan Yuan; et al. (Marine Pollution Bulletin, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

A probabilistic prediction model based on uncertainty quantification and interpretable deep learning: Application to runoff prediction in the Yellow River mainstream - Liang Mu; Junxi Chen; Zhiguo Yu; Hong Zhao; Zhibo Yang (Journal of Hydrology, 2026)

Static magnetic field coupled with magnetic biochar boosts methane production in sludge anaerobic digestion by activating dual electron transfer mechanisms - Likui Feng; Muzi Li; Kaiyi Zhang; Shuo Liu; Heng Liang; Zhelu Gao; Huizhi Mu; Shufei He; Qingliang Zhao; Liangliang Wei (Journal of Environmental Chemical Engineering, 2026)

Metal-phenolic network coordination-mediated assembly of whey protein isolate gels: Structural evolution, functional attributes, and digestive behavior - Jinzhe Li; Zhishen Mu; Mingzhang Zhao; Munkh-Amgalan Gantumur; Purevjav Mejeenov; Zhanmei Jiang; Juncai Hou (Food Research International, 2026)

Stepwise hydrolysis reduces allergenicity of α-lactalbumin through epitope removal and structural modulation - Qing Zhao; Guangqing Mu; Ruida Ma; Qi Sun; Peng Sun; Xiaomeng Wu; Fanhua Kong (Food Research International, 2026)

Unlocking the antioxidant potential of wheat gluten: structural transitions and peptide release driven by ultrasonication-assisted pH shifting - Peng Cheng; Xueying Song; Yihan Mu; Siliang Wu; Mouming Zhao; Guowan Su (Food Chemistry, 2026)

Simultaneous elimination of sulfonamides and antibiotic resistance genes via peroxymonosulfate activation by ligand-modulated iron sites on biochar: The critical role of interfacial EDTA complexation - Yifan Liu; Fengxia Yang; Xue Li; Zhikang Deng; Xi Chen; Minghui Xiang; Ran Zhao; Xiaoquan Mu; Yongzhen Ding; Junjie Wang; Zulin Zhang (Chemical Engineering Journal, 2026)

Engineering an “nano-antibiotic”: Synergistic catalytic bacterial killing via metal-phenolic network accelerating Fe(III)/Fe(II) cycle on MIL-101(Fe) - Qin Zhang; Xiaoming Song; Yifan Zhou; Lulu Pan; Xuemin Mu; Xiaolin Wang; Yanyan Li; Xiuhua Zhao (Chemical Engineering Journal, 2026)

Discovery of thiol-reactive Staphylococcus aureus sortase A inhibitors from natural products by machine learning and thiocholine mass-shift profiling - Yujing Huang; Congzhen Shen; Xiaoqing Mu; Chengyin Huang; Shasha Zhao; Jinlian Liang; Zhipeng Gu; Yingxin Zhang; Zezhong Yang; Jianni Yang; Haibo Zhou; Pinghua Sun; et al. (Analytica Chimica Acta, 2026)

Improving offshore aquaculture governance in China: policy structure assessment using PMC-Index and text mining - Chang Gao; Chao Zhao; Md Hashmi Sakib; Yongtong Mu (Aquaculture, 2026)

Tannic acid protects against lapatinib-induced hepatotoxicity by inhibiting cathepsin activity and repairing lysosomal membrane permeabilization - Yuan Mu; Zengyue Pan; He Zhao; Xiangliang Huang; Nini Zhang; Zhifei Xu; Bo Yang; Qiaojun He; Xiaochun Yang; Peihua Luo; Hao Yan (Toxicology and Applied Pharmacology, 2026)

Integrated genomic and functional analyses reveal model-dependent immune modulation by human milk-derived Limosilactobacillus reuteri DPUMW-M12-9 - Zhao Zhang; Yanchen Liu; Zhaobin Yan; Yaqi Hou; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2026)

An enhanced and humidity-adaptive chitosan foam triboelectric nanogenerator: Multi-component synergistic design for energy harvesting and sensing applications - Jie Tao; Qiangli Zhao; Jiahao Kang; Min Mao; Qiang Mu; Tao Jiang; Lanjin Wang; Panxu Wang; Xiao Han; Xinhai He; Jianwei Li (Carbohydrate Polymers, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

A global-local multi-scale feature extraction network for fine-grained segmentation of cyanobacterial blooms and aquatic vegetation - Yunchang Mu; Junsheng Li; Huan Zhao; Xiaodi Zhu; Zeyan Zhang; Fangfang Zhang; Shenglei Wang (Journal of Oceanology and Limnology, 2026)

Influence of inclination angle on the failure mechanisms and shear capacity of concave-convex tenon connections in shield tunnel joints - Haixing Mu; Kun Feng; Jialin Li; Jiaqi Li; Wenqi Guo; Yili Zhou; Lixiang Zhao; Chuan He (Tunnelling and Underground Space Technology, 2026)

Combined exposure to flumethrin and hexaconazole induces synergistic oxidative, metabolic, and immune dysregulation in honeybees - Tao Cang; Ying Wang; Xinfang Li; Xin Peng; Qihe Zhao; Xiyan Mu; Guojun Zhou; Yanhua Wang (Journal of Hazardous Materials, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

Novel ex-situ functionalized bacterial cellulose-based packaging films with full hydrogen-bonded network for sustainable and bio-safety food preservation - Changqing Zhao; Lang Wu; Jiao Huang; Liguo Yin; Jiawei Wang; Zihao Feng; Lin Bai; Xingxiu Zhao; Zhifeng Zhao; Shengdong Mu (Food Research International, 2026)

Zwitterionic imprinting enables fouling-resistant biomimetic sensing of Staphylococcus aureus in complex food matrices - Zhi Zeng; Manru Zhao; Zhongrui Ma; Yufei Mu; Xiaoya Li; Yanqun Wang; Ying Chen (Food Chemistry, 2026)

Aldo/keto reductase regulates L-lactate dehydrogenase activity as a key target for yogurt post-acidification - Qingqing Mu; Sitong Jia; Dongyao Li; Whenhao Zhao; Na Zhang; Miaoshu Wang; Hongtao Tian; Chen Li (Food Microbiology, 2026)

A long-term fracture conductivity model for shale considering non-linear creep damage, proppant elastic-elastoplastic-plastic embedment, and hydration swelling effects - Shuxing Mu; Lianheng Zhao; Ao Zhang; Sanfeng Liu (Computers and Geotechnics, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

Differential driving mechanisms on saline-alkali land in desert and oasis of arid and semi-arid regions - Lei Zhang; Xia Jia; Yonghua Zhao; Manya Luo; Qi Mu; Peng Zhang; Yu Bai (CATENA, 2026)

ROS regulate pollen germination and tube growth in Betula platyphylla with involvement of H2O2 and polyamine oxidase BpPAO2 - Chaoning Zhao; Wendi Mu; Jiaqi Shi; Jiayuan Shi; Bello Hassan Jakada; Gege Dou; Taihe Zhao; Huiyi Xie; Siyu Dong; Ying Wu; Xingguo Lan (Physiology and Molecular Biology of Plants, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

Temporal-spatial variation, source apportionment, and health risk assessment of DDT residues in bivalve species from the coastal areas of Zhejiang, China - Xinjian Yu; Guoquan Wang; Xiaohua Wang; Qinghong Zhang; Yanjian Jin; Weihong Zhao; Jian Wang; Penglei Guo; Fengfan Chen; Xiaoqing Liu; Xian Sun; Dongsheng Qian; et al. (Ocean & Coastal Management, 2026)

Tetramethylpyrazine promotes spinal cord injury repair by modulating macrophage M1/M2 polarization via inhibition of the IL-6/JAK2/STAT3 pathway - Huizhong Bai; Luyao Huo; Ruiqin Yu; Bowen Deng; Jiashu Yue; Yu Jiang; Yimin Zhou; Yi Zhao; Xiaohong Mu (Toxicology and Applied Pharmacology, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Unveiling the S-scheme charge transfer in MOF-808/PPy heterojunctions for enhanced Se(IV) photoreduction and subsequent mercury capture - Yu Liang; Xueqing Zhang; Yirui Li; Xiangyu Xiao; Tingmei Ma; Xiao Mu; Jing Zhao; Jiayiwen Wang; Huanhuan Xiao; Jiaxu Zhang (Process Safety and Environmental Protection, 2026)

Dynamics aware spatio-temporal path planning for USV in reef–island waters under time-varying environmental disturbances - Ziang Wang; Dongdong Mu; Yongsheng Zhao; Xiao Liang; Yunsheng Fan (Ocean Engineering, 2026)

A precise underwater positioning method by considering TDOMA under fluctuating sea surface - Xukai Mu; Zhenxing Zhao; Wei Gao (Ocean Engineering, 2026)

Characterization and mechanistic insights into changes in flavor compounds of yeast extract during the evaporative process - Yuting Liu; Siliang Wu; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Innovative Food Science & Emerging Technologies, 2026)

Grain quality, texture characteristics, and starch fine structure of ratoon rice practiced with high stubble height: Insights from panicles regenerated at different stem nodes - Wanfeng An; Mingji Yu; Ruixue Yu; Shuiyin Yang; Jiali Miao; Qingyao Huang; Jizhe Mu; Jianquan Qin; Chang Zheng; Xiaoyan Song; Quanzhi Zhao (Food Research International, 2026)

A new strategy to reduce casein antigenicity: Investigating immune response, gut microbiota dysbiosis, and metabolic changes in allergic mice - Qi Sun; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong; Guangqing Mu (Food Chemistry, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Copper-doped Bi2Te3 thermoelectric nanorods in electrospun fabrics for breath-activated antibacterial masks - Linghui Lyu; Yihong Liu; Yongting Xie; Yuqing Li; Bowen Jin; Yuyan Zou; Henan Zhao; Yinghao Mu; You-Nian Liu; Jianghua Li; Wansong Chen (Chemical Engineering Journal, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Soil health assessment of natural coniferous-broadleaved mixed forests in the Changbai Mountains using structural equation modeling - Chen Mu; Haiyan Wang; Xue Cui; Han Zhao; Jiahe Zou (Journal of Soils and Sediments, 2026)

Coupled atmosphere-ocean data assimilation for enhanced medium-range prediction of the North Atlantic Oscillation - Bin Mu; Zijun Zhao; Shijin Yuan; Bo Qin; Guokun Dai (Science China Earth Sciences, 2026)

Environmental filtering drives microbial niche shift from generalists to specialists during the aging of proglacial lakes - Xiaodong Li; Bingya Zhang; Qing Yang; Zhao Xue; Guangli Mu; Meiqi Huang; Qianggong Zhang; Jinrong Huang; Yingxin Zhao; Yindong Tong (Limnology and Oceanography, 2026)
Global warming is altering material cycles in cryospheric and aquatic ecosystems. Accelerated glacier retreat has spurred the formation of numerous proglacial lakes, providing ideal natural laboratories for studying early ecological succession. However, the mechanisms driving microbial succession as these lakes age, particularly shifts in niche strategies and community assembly, remain poorly understood. We investigated 12 proglacial lakes at distinct developmental stages on the central Qinghai‐Tibet Plateau, with formation dates ranging from before the 1980s to 2020. By integrating 16S/18S rRNA sequencing, molecular networks, and null models, we characterized microbial successional trajectories along this gradient. As lakes aged, α‐diversity decreased whereas β ‐diversity increased for both bacteria and eukaryotes, and this β ‐diversity shift was primarily attributable to species turnover. These changes coincided with systemic niche contraction and network simplification, leading to a significant decline in community stability. Notably, assembly processes differed between bacteria and eukaryotes. Bacterial communities shifted from stochasticity to homogeneous selection, whereas eukaryotic assembly was consistently governed by dispersal limitation. Functionally, bacteria transitioned from high‐cost stress‐response traits such as cold shock proteins to efficient nutrient biosynthesis including histidine and lysine. Together, these findings advance our understanding of divergent microbial succession and assembly mechanisms in proglacial lakes, providing critical insights into ecosystem development under climate‐driven glacier retreat.

Analysis of the Resistance Performance for a High-Speed Planing Craft Under Various Longitudinal Center of Gravity Positions - Qiaosheng Zhao; Qitian Fang; Guoqing Jin; Chaoxu Mu; Dejun Li; Xuyu Ouyang; Kuilin Yuan (Journal of Marine Science and Engineering, 2026)
The accurate prediction of resistance and running attitudes of high-speed planing crafts is of great significance for the improvement of ship hydrodynamics. In this study, the lab model tests and computational fluid dynamics (CFD) methods are employed to investigate the effects of volumetric Froude number and longitudinal center of gravity (LCG) position on the resistance performance, motion characteristics, and free-surface wave patterns for a planing craft. The capability of the CFD model was validated through towing tank resistance tests conducted under various LCG conditions. A systematic analysis of the influence mechanism of LCG variation on the hydrodynamic performance of the craft was conducted. The results indicate that an aftward LCG position can improve the resistance performance; however, it also leads to an increase in the pitch angle. These findings can provide a foundation for the optimization design of high-speed planing craft.

A systematic identification and characterization of long noncoding RNAs during abiotic stress in Medicago truncatula - Kanghua Du; Yingan Zhu; Weiyu Yan; Ting Gao; Wanfu Mu; Ziwei Zhao; Zhong Dan; Xiaolu Meng; Haoting Chen; Yan Zhao; Jie Zhang (Journal of Plant Physiology, 2026)

Enhancing copper ion capture in MXene through oxygen content modulation - Lihao Zhao; Jie Jiang; Jiahao Hu; Ningyu Zhang; Pei Li; Yanghui Li; Junbo Wang; Liuhua Mu; Liang Chen (Journal of Environmental Chemical Engineering, 2026)

Coupling plasmonic hot-carrier generation and Schottky junctions in 1T-WS2/CuInS2 for enhanced photothermal CO2 reduction - Sihan Zhao; Siting Ma; Chenhao Yuan; Fahim A. Qaraah; Changjiang Sun; Xia Li; Manman Mu; Xiaohong Yin (Journal of Environmental Chemical Engineering, 2026)

Stage-specific environmental responses and divergent distributional shifts of Antarctic krill under climate change in the Cosmonaut Sea - Xiuxia Mu; Xianyong Zhao; Chongliang Zhang; Yunxia Zhao; Qingchang Xu; Jichang Zhang; Yiping Ying; Lu Liu; Jianfeng He; Peiru Luo; Xinliang Wang (Journal of Environmental Management, 2026)

Comparison of nitrogen oxides (NO, NO2) analyzers from controlled conditions in a 100 m3 outdoor simulation chamber to field observations - Xuanming Huang; Xiaowei He; Jinzhao Tong; Baobin Han; Shichuan Ni; Zhiwei He; Xuelian Zhong; Xinmiao Xu; Min Cai; Yang Wang; Chenyang Xue; Wenya Niu; et al. (Journal of Environmental Sciences, 2026)

Substantial discrepancies across global fire emissions inventories: a systematic intercomparison - Jiyuan Yang; Hanyue Zheng; Peng Zhao; Johannes W. Kaiser; Qing Mu (Journal of Environmental Sciences, 2026)

Antibacterial mechanism of combined high-voltage electrostatic field and low-temperature energy field against Bacillus cereus in milk sources - Zhaobin Yan; Guibing Pang; Zhao Zhang; Xiaomeng Wu; Guangqing Mu; Hui Zhang (Innovative Food Science & Emerging Technologies, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

K isotope behavior in topsoil from the southeastern margin of the Tibetan Plateau - Yanan Cheng; Jun Mu; Peizheng He; Cheng Cao; Shichao An; Can Zhang; Xiaoping Feng; Cheng Zhao; Xiao-Ming Liu (Geochimica et Cosmochimica Acta, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Fabrication of debranched pea starch beads through gellan gum self-assembly and ionic cross-linking for enhanced digestive resistance - Lu Yang; Ziyun Zhao; Hongyan Mu; Yang Qin; Liu Xiong; Shucheng Zhang; Qingjie Sun (Carbohydrate Polymers, 2026)

Soil infiltration responses to vegetation restoration along a precipitation gradient on the loess plateau - Shuyu Zhang; Guangju Zhao; Yuanhao Liu; Peng Tian; Xingmin Mu (CATENA, 2026)

Intestinal-Protective Lactiplantibacillus plantarum DPU-MWM14-103 Exhibits Genomic Adaptations and Multifaceted Probiotic Properties - Zhao Zhang; Yanchen Liu; Baoyuan Zhao; Zhaobin Yan; Xuemei Zhu; Guangqing Mu; Xiaomeng Wu (Probiotics and Antimicrobial Proteins, 2026)

BiSSET-Net: Multi-factor Time Series Prediction of Pine Caterpillar Infestation Risk in Northeast China Based On Bidirectional LSTM and State Space Model - Jingzheng Zhao; Mingchang Wang; Xi Mu; Dong Cai; Fengyan Wang; Minshui Wang; Hongchao Fan (Journal of Geovisualization and Spatial Analysis, 2026)

Cold Stress and Molecular Adaptations in Aquatic Organisms: A Comparative Review of Fish, Crustaceans, and Mollusks - Lan Li; Yihong Mu; Chunrong Zuo; Minfang Zhao; Zhiqiu Huang; Wenli Zhang; Meihong Qiu; Yi Huang (Fishes, 2026)
Cold stress poses a significant challenge to aquatic organisms, affecting their survival, growth, and metabolic processes. This review explores the molecular mechanisms by which fish, crustaceans, and mollusks respond to cold stress, highlighting the shared and species-specific pathways that facilitate adaptation. Common responses to cold stress include modulation of energy metabolism, regulation of oxidative stress, immune responses, and maintenance of proteostasis. In particular, the activation of the adenosine 5′-monophosphate-activated protein kinase (AMPK) and mechanistic target of rapamycin (mTOR) pathways plays a critical role in regulating energy balance and autophagy in response to low temperatures. Furthermore, we examine the specific adaptive mechanisms employed by different groups of aquatic organisms. Fish utilize pathways such as peroxisome proliferator-activated receptor alpha/peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PPAR/PGC-1α) and fatty acid oxidation to optimize energy utilization and improve cold tolerance. Crustaceans rely on crustacean hyperglycemic hormone (CHH) signaling and AMPK pathway activation, while mollusks employ metabolic suppression and glycogen storage to survive cold exposure. Moreover, the regulation of autophagy and apoptosis, mediated by p53 and cyclin-dependent kinase 1 (Cdk1), ensures the survival of healthy cells under prolonged cold stress, with autophagy maintaining energy homeostasis and apoptosis eliminating damaged cells. This review also discusses the role of molecular chaperones like heat shock protein 70 (HSP70) and the ubiquitin-proteasome system (UPS) in protein homeostasis, highlighting their importance to protect cells under cold stress. The combined action of these molecular pathways allows aquatic organisms to cope with and adapt to cold environments, ensuring cellular integrity and enhancing survival. Future research should focus on integrating molecular, physiological, and ecological approaches to better understand cold tolerance mechanisms and improve aquaculture practices under climate change scenarios.

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Immunogenicity Assessment for siRNA Therapeutics: A Risk-Based Proposal for Event-Driven Testing - An Zhao; Sarah Bond; Valerie Clausen; Mu Chen; Ching-Ha Lai; Joshua Zylstra; Christine Grimaldi; Michael A. Partridge (The AAPS Journal, 2026)

Palatability-by-Design for Oral Drug Products: A Unified Framework for Evaluation and Optimization - Qiaorui Li; Junzhe Xi; Zhenda Liu; Yingying Mu; Lijie Zhao; Lan Shen (AAPS PharmSciTech, 2026)

Numerical Investigation of Poisson’s Ratio Effects on Ice–Structure Interaction Using the Peridynamic Method - Yuan Zhang; Liyu Ye; Chao Wang; Xiuyuan Zhang; Dagang Zhao; Jinlei Mu; Shan Pian; Biliang Lu (Journal of Marine Science and Engineering, 2026)
The peridynamic (PD) method has been widely utilized in the numerical modelling of ice–structure interactions due to its capability to naturally capture material failure and fracture evolution. PD formulations can be categorized into bond-based and state-based models. While the bond-based model offers computational simplicity, it inherently restricts Poisson’s ratio to 1/4 in three-dimensional (3D) simulations and 1/3 in two-dimensional (2D) simulations. In contrast, the state-based model allows for arbitrary Poisson’s ratios, which is essential for accurately modelling ice mechanics, as Poisson’s ratio of ice commonly exceeds 0.33 and can reach up to 0.42. This study employs the PD method coupled with the discrete energy release rate criterion to analyze the influence of Poisson’s ratio on ice failure mechanisms and ice-induced loads in two typical scenarios: cylindrical impact on an ice disc and ice–structure interaction with a propeller blade. The benchmark compression test yielded computed Poisson’s ratios of 0.215, 0.258, 0.333, and 0.401 for prescribed values of 0.2, 0.25, 0.33, and 0.40, corresponding to relative errors of 7.5%, 3.2%, 1.02%, and 0.38%, respectively. And the fracture simulations indicate that variations in Poisson’s ratio affects ice fracture patterns and load distributions, underscoring the limitations of the bond-based PD model in accurately representing ice–structure interactions. These findings highlight the necessity of adopting state-based PD formulations for improved numerical predictions of ice-induced mechanical responses.

Artificial intelligence for ocean phenomena forecasting - Xiaofeng Li; Xudong Zhang; Yibin Ren; Yunhe Wang; Nan Yang; Chong Wang; Shanshan Mu; Haoyu Wang; Yuan Zhou; Yingjie Liu; Zimeng Zhao; Fan Wang (Science Bulletin, 2026)

The effect of high-voltage electrostatic field combined with low-temperature hybrid energy field on the protein structure and antioxidant properties of pasteurised milk - Zhaobin Yan; Hui Zhang; Zhao Zhang; Xiaomeng Wu; Guangqing Mu; Guibing Pang (Innovative Food Science & Emerging Technologies, 2026)

IgG release and peptides production by trypsin-driven selective hydrolysis of casein in bovine colostrum to improve immunomodulatory activity - Ying-Chao Qiu; Meng-Jiao Wang; Zi-Ying Zhao; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

An infant-derived Bifidobacterium pseudocatenulatum DPU-MWF3-6 strain exhibits favorable in vitro functional properties and is well tolerated during early life in neonatal rats - Zhao Zhang; Yanchen Liu; Fanhua Kong; Yinglong Song; Yaowei Liu; Xiaomeng Wu; Guangqing Mu (Food Bioscience, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

Sequential release of photodynamic hybrid HOFs and CeO₂ via a bilayer dynamic SIS hydrogel for periodontitis therapy - Shiqing Ma; Yujia Xiao; Yang Yu; Xiaotong Liu; Jiayin Deng; Yilin Yang; Shiyu Yao; Beibei Ma; Yo Shibata; Jun Zhou; Bo Zhao; Yuzhu Mu (Chemical Engineering Journal, 2026)

Establishment of a Hybrid Snakehead Spleen Cell Line for Viral Studies - Xuanming Liu; Qing wang; Xiudong Guo; Yingying Li; Xubing Mo; Jiyuan Yin; Shucheng Zheng; Jian Zhao; Xidong Mu; Yingying Wang (Journal of Fish Diseases, 2026)
A spleen‐derived cell line was established from the spleen of hybrid snakehead (♀ Channa argus × ♂ Channa maculata ) (abbreviated as CAMsp ), a species of considerable economic importance in China's freshwater aquaculture, which is severely impacted by the hybrid snakehead rhabdovirus ( HSHRV ), largemouth bass ranavirus ( LMBV ), and infectious spleen and kidney necrosis virus ( ISKNV ). The establishment of a stable in vitro culture system is imperative for the effective isolation, identification, and study of fish viruses. CAMsp , generated through trypsin digestion, had successfully undergone over 80 passages since its initial culture. This cell line exhibited rapid proliferation in Leibovitz's‐15 medium (L‐15) supplemented with 10% fetal bovine serum at 28°C, achieving monolayer formation within 24 h at a passage ratio of 1:3. Chromosomal analysis of CAMsp at the 60th passage identified a chromosome count of 42; the chromosome number in hybrid snakehead somatic cells is 44, 45, or 46, suggesting chromosomal alterations. Inoculation of CAMsp monolayers with HSHRV , LMBV , and ISKNV resulted in characteristic cytopathic effects ( CPE ), including cell rounding, aggregation, and eventual detachment. Transmission electron microscopy ( TEM ) confirmed viral replication and revealed extensive cytopathological changes within the infected cells, demonstrating the susceptibility of the CAMsp cell line to all three viruses. Viral titers, determined by TCID 50 assay at 7 days post‐infection (dpi), reached 10 9.25 ± 10 0.36 TCID 50 / mL for LMBV , 10 6 · 15 ± 10 0.25 TCID 50 / mL for ISKNV , and 10 8 · 33 ± 10 0.12 TCID 50 / mL for HSHRV , indicating efficient viral propagation in this cell line. The CAMsp cell line serves as a valuable model for studying certain fish viruses, virus‐host interactions, and disease prevention strategies.

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Unmanned surface vehicle path-following under time-varying wave encounter angle: Simulation and field experiment - Ziang Wang; Yongsheng Zhao; Dongdong Mu; Guibing Zhu; Xiaojie Sun (Ocean Engineering, 2026)

Physics-guided transformer-based modeling for surface water quality prediction in aquatic environments - Zehui Mu; Hairong Jiang; Jumin Zhao; Dengao Li; Zhenjie Gong; Shan Xue (Journal of Water Process Engineering, 2026)

N-doped ordered mesoporous carbon embedded with Ni-N₃-Pyr sites achieve nearly 100% selectivity for CO₂RR to CO - Di Jin; Yunpeng Zou; Yang Zhao; Shuai Chen; Shiwei Luo; Taotao Chen; Jinchuan Zhang; Jialin Chen; Jijie Li; Yuewen Mu; Wen-Yan Zan; Fengwei Zhang (Journal of Environmental Chemical Engineering, 2026)

Geographical-XGBoost and SHAP reveal ecosystem service supply-demand responses to landscape patterns in karst regions - Yurong Han; Jiayi Yin; Dayun Zhu; Jiaying Tan; Yingshan Zhao; Wanqing Liu; Yurong Mu (Journal of Environmental Management, 2026)

Layered double hydroxides vs. metal-organic frameworks: Which enables more sustainable phosphate fertilizer production from sludge? - Xiaole Wang; Qian Zhao; Xiaoxiang Cheng; Jingtao Xu; Shujuan Meng; Yifan Zhao; Kechao Han; Ruimin Mu; Lei Liu (Journal of Environmental Chemical Engineering, 2026)

Photoelectrotrophic denitrification and iron-sulfur-nitrogen cycle enhance nutrient removal in pyrite-amended constructed wetlands - Xiaoxiao Hou; Lingyun Mu; Yingying Liu; Yanping Xiao; Xinshan Song; Xiaoxiang Zhao; Dong An (Journal of Environmental Management, 2026)

In situ natural-ester-grafted coating extends cellulose insulation paper service life: Hydrophobicity and thermal-aging resistance for high-voltage equipment - Wenrui Tian; Haoxiang Zhao; Haibao Mu; Huanmin Yao; Xiong Yang; Jiufeng Dong; Daning Zhang; Guanjun Zhang (Chemical Engineering Journal, 2026)

Sustainable and selective gold extraction from electronic waste using conjugated microporous polymer aerogels - Wei Liu; Zhaoqi Zhu; Xicheng Liu; Mengqi Zhao; Rui Jiao; Peng Mu; Hanxue Sun; An Li (Chemical Engineering Journal, 2026)

Tailoring nitric oxide-release hydrogel incorporating MSC-derived exosomes for multimodal therapy of diabetic foot ulcers - Kaijie Zhao; Xuan Tian; Qijian Wei; Yuteng Li; Mingzhuo Zhou; Anhui Mu; Xin Yan; Shilei Ni; Pei Liu (Chemical Engineering Journal, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Effect of sodium nitroprusside (SNP) on drought stress mitigation through wax accumulation in Lagenaria siceraria (Molina) Standl.: an integrated GC–MS and transcriptomic approach - Shan Liu; Xiaodi Zhang; Saike Qi; Li Geng; Wenchao Zhao; Yulu Gao; Hongmei Mu (Plant Cell Reports, 2026)

Dihydrotestosterone binding to the androgen receptor inhibits apoptosis in ovine undifferentiated granulosa cells via AMH signaling - Yufen Zhao; Haijiang Liu; Zhe Mu; Haijun Li (Animal Reproduction Science, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Quantifying the impacts of increasing light and moderate rainfall on permafrost thermal regimes over the Qinghai-Tibet Plateau: A controlled sensitivity study - Guofei Zhang; Cuicui Mu; Yining Zhang; Xiaofan Zhu; Yi Zhao; Zhuotong Nan (Journal of Hydrology, 2026)

The synergistic effect of algal-bacterial granular sludge in a sequencing batch reactor with tetracycline-containing synthetic livestock and poultry breeding wastewater - Yuanda Du; Shoubo Zhao; Yanan Gao; Yujie Yan; Yi Kong; Wenwen Meng; Xinru Lu; Shun Zheng; Haolin Mu; Xiaojing Chen; Qiang Kong (Journal of Environmental Management, 2026)

Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Glacial melting enhances the influence of microbial cross-domain interactions on dissolved organic carbon dynamics across the high-altitude glacier-proglacial lake-river continuum - Yanan Zhou; Qing Yang; Hongyang Cui; Meiqi Huang; Zhao Xue; Guangli Mu; Feng Zhao; Liang Li; Xiaodong Li; Yindong Tong (Journal of Environmental Sciences, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Molecular characteristics of water-soluble organic aerosols under pollution conditions in a coal resource-based city revealed by FT-ICR MS: a significant role of sulfur-containing compounds - Chao Zhang; Ziyong Guo; Qingyu Hu; Lin Qi; Yang Chen; Yufeng Zhao; Nan Pei; Wei Sun; Xiaodong Hu; Yuxiang Yang; Fengxian Liu; Ling Mu; et al. (Fuel, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Bidirectional aeolian erosion controls the spatial variations of yardang landforms in Dunhuang yardang National Geopark, Northwestern China - Yongchong Lin; Chunyao Wu; Guijin Mu; Jifeng Zhang; Cong Zhao (Aeolian Research, 2026)

Low-glutelin rice as a food-based strategy for protein restriction: Genetic development, structural engineering, and nutritional consequences - Ying Mei; Yuwei Hua; Yuxin Mu; Qiang Liu; Siqi Zhao; Xinbo Zhuang; Chao Ding; Liping Guo (Trends in Food Science & Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Risks and underling mechanisms of sulfoxaflor exposure in honey bees (Apis mellifera): Physiology and behavior impairment - Mu Ding; Xue Wang; Wei Zhang; Aidi Huang; Wenting Zhao; Mai Luo; Liming Wu; Suzhen Qi (Pesticide Biochemistry and Physiology, 2026)

Sustainable synthesis of phosphate/silicate/biochar composites derived from oil shale semi-coke waste for efficient adsorption and passivation of heavy metals - Dandan Wang; Bin Mu; Feng Zhao; Yan Liu; Yongfeng Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2026)

Recent advances and prospects of iron-based biochar for antibiotic removal: Unveiling the dual mechanisms of adsorption and degradation - Junjie Wang; Yifan Liu; Xue Li; Ran Zhao; Xiaoquan Mu; Fengxia Yang; Haixin Guo; Yongzhen Ding (Journal of Environmental Chemical Engineering, 2026)

Fe3O4 nanoparticles and cytochrome c synergistically facilitate lactate chain elongation to caproate - Yichao Wang; Chunhui Zhao; Fangyuan Feng; Yaomin Xi; Wenhan Chen; Xiaoyu Zhu; Xiang Li; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2026)

Enzymatic hydrolysis of bovine casein assisted by microfluidization: Effects on functional properties and identification of anxiolytic peptides - Meng-Jiao Wang; Zi-Ying Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Creating syngas and sulphur from H2S and CO2 over Mo-Cu based catalyst in a dielectric barrier discharge reactor - Lu Zhao; Wenshuang Feng; Xiaoliang Mu; Kegong Fang (Fuel, 2026)

Microbial succession–potential influence mechanism on flavor modulation in spontaneously fermented Moringa oleifera leaves: An integrative multi-omics approach - Yuhan Liu; Yuwei Guo; Hongyu Mu; Muhammad Aaqil; Feng Zhang; Jingchuan Zheng; Jun Sheng; Yang Tian; Cunchao Zhao (Food Research International, 2026)

Sugarcane polyphenols modulate gut microbiota and odor-associated metabolites during in vitro fecal fermentation of elderly - Hongye Li; Yun Bian; Yi Wu; Xueqing Hang; Mengqing Zhang; Luchuan Gao; Yifei Dong; Tanhang Mu; Wei Zhao (Food Bioscience, 2026)

Ultrasonic enhanced Fe-C/PDS system for sludge dewatering and carbon source release: synergy of oxidation and cracking processes - Wenye Li; Binghan Xie; Zhipeng Li; Guoyu Zhang; Zhiying Lv; Qinghao Li; Shuyu Zhao; Mu Tong; Yuanyuan Gao; Langming Bai (Bioresource Technology, 2026)

Research progress on exogenous substances and their mechanisms of action in alleviating low-temperature stress in plants - Jiayi Chen; Qian Zhou; Qiong Wu; Jun Yang; Bihui Huang; Wenli Mu; Qinshuang Mei; Heping Zhao; Haifang Hu; Fenglan Liu; Jing Guo; Huixin Zhao (Planta, 2026)

CCT7 predicts poor prognosis and correlates with immune infiltration in colonic adenocarcinoma - Wenxu Li; Qizhong Shi; Yonghui Mu; Chenglei Li; Wenchao Zhao; Na Han (Journal of Molecular Histology, 2026)
CCT7, a member of the t-complex polypeptide 1 chaperone family, facilitates ATP-dependent protein folding; however, its role in development and progression of malignant tumors remains unclear. This study aimed to characterize the expression pattern of CCT7 in colonic adenocarcinoma (COAD) and evaluate its role in the initiation and development of COAD. Public bioinformatic databases were analyzed to assess CCT7 expression in COAD, and these findings were validated using human clinical specimens through immunohistochemistry (IHC) assay. The prognostic significance of CCT7 was examined using Kaplan–Meier method and Cox regression analysis. Gene Ontology-Biological Process (GO-BP) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the potential biological functions and downstream pathways associated with CCT7. CCK-8, colony formation and Transwell assays were conducted to determine the impact of CCT7 on cell proliferation, migration and invasion in COAD cell lines. Associations between CCT7 expression and immune cell infiltration or drug sensitivity were evaluated using single-sample gene set enrichment analysis and correlation analysis. Finally, immune checkpoint inhibitor therapy scores and their relationship with CCT7 expression were assessed using data from The Cancer Immunome Atlas. CCT7 expression was significantly up-regulated statistically in COAD tissues compared with normal colonic tissues ( P < 0.05) and elevated CCT7 levels were associated with poorer prognosis of COAD patients ( P < 0.05). GO-BP enrichment analysis indicated that CCT7 was primarily involved in the processes related to cell proliferation and microtubule organization ( P < 0.05). Consistently, functional assays confirmed that CCT7 knockdown inhibited COAD cell proliferation, migration, and invasion ( P < 0.05). CCT7 expression showed a negative correlation with infiltration of most immune cell types ( P < 0.05) and demonstrated no significant association with predicted responses to PD-1 and CTLA-4 inhibitor therapies ( P > 0.05). Moreover, drug sensitivity analyses showed that CCT7 affected the sensitivity of COAD samples to several anti-cancer drugs ( P < 0.001). KEGG enrichment analysis revealed that CCT7 was associated with multiple pathways ( P < 0.05). CCT7 may function as an oncogenic driver that promotes the malignant phenotype of COAD and represents a promising prognostic biomarker. It may also provide a valuable reference for guiding clinical therapeutic strategies in COAD.

Insight into the Evolution of Mitochondrial Genetic Basis of Amphibious Adaptation in the Goby (Teleostei: Gobiidae) - Chengyao Yang; Chaoyang Luo; Qiuping Wang; Xionghui Xu; Juan Zhang; Chengfa Zhao; Yuan Mu; Datian Lang; Wenxian Hu (Journal of Molecular Evolution, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Comparative nutritional outcomes in preterm infants and formulation optimization of infant formula: a review - Yanchen Liu; Zhao Zhang; Guangqing Mu; Xuemei Zhu (Critical Reviews in Food Science and Nutrition, 2026)

COLREGs-compliant ship collision avoidance strategy based on proximal policy optimization algorithm - Qiaosheng Zhao; Tianyu Yang; Chaoxu Mu; Qiyu Chen; Tao Luo; Mingkai Liu; Xin Wang (Frontiers in Marine Science, 2026)
The safe and efficient collision avoidance of multiple ships is essential for maritime navigation and intelligent shipping systems. In this paper, we propose a novel COLREGs-compliant multi-ship collision avoidance strategy based on deep reinforcement learning. A cooperative training framework using the Proximal Policy Optimization (PPO) algorithm enables multiple ship agents to learn optimal collision avoidance actions while considering the interactions and motions of neighboring ships. Encounter situation awareness mechanisms and carefully designed reward functions are integrated to ensure strict adherence to the International Regulations for Preventing Collisions at Sea (COLREGs), while a multi-objective optimization approach embedded in the reward function balances collision risk, navigational efficiency, route smoothness, and destination achievement. Extensive simulations covering diverse ship encounter scenarios demonstrate the effectiveness, robustness, and COLREGs compliance of the proposed strategy, highlighting its practical potential for multi-ship navigation systems.

Gonadal Transcriptome Analysis Identifies Sex-Related Genes and Regulatory Pathways in Spotted Longbarbel Catfish (Hemibagrus guttatus) - Kun Zhao; Yuanyuan Wang; Yexin Yang; Yi Liu; Chao Liu; Shandian Zhu; Jinhui Sun; Xidong Mu (Fishes, 2026)
Hemibagrus guttatus is a large omnivorous fish of significant economic value, listed as a Class II protected species in the National Key Protected Wildlife List in 2021 in China. To provide a theoretical foundation for the artificial breeding of H. guttatus, this study employs high-throughput transcriptome sequencing of testes and ovaries to elucidate the molecular regulatory pathways involved in sex differentiation. Because H. guttatus exhibits no obvious sexual dimorphism even during the breeding season, the distinctive contribution of this study compared with previous gonadal-transcriptomic investigations in other Siluriformes lies not only in documenting sex-biased genes but also in providing a molecular foundation for developing non-lethal sex-identification methods for this morphologically indistinguishable species. A total of 303,192,896 raw reads were obtained, with an effective data rate of 98.4%, indicating high sequencing quality. Differential expression analysis identified 8694 genes, including 6369 upregulated in testes and 2325 upregulated in ovaries. Among these, 88 genes were functionally annotated as sex-related, with 62 testis-biased genes such as spata17, sox9, and dmrt1, and 26 ovary-biased genes including cyp19a, wnt8, and sox12. KEGG pathway enrichment analysis revealed that the TGF-β signaling pathway, insulin secretion, and steroid hormone biosynthesis may play crucial roles in gonadal development and differentiation in H. guttatus. The expression patterns of key genes such as hsd11b1, amh, and insl3 were validated by quantitative real-time PCR, showing consistency with the transcriptome results. These findings lay a molecular foundation for understanding the regulatory mechanisms of sex differentiation in H. guttatus, and provide candidate genes for further investigation into the genetic basis of gonadal development, which is essential for improving artificial reproduction and selective breeding practices.

Effects of photoperiods on hypothalamic-pituitary-interrenal (HPI) axis and immune responses in high latitude fish Phoxinus lagowskii - Xiaoyu Zhao; Yiwen Liu; Weichen Wang; Yi Chang; Tingting Hu; Kai Ma; Weijie Mu (Aquaculture, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Decoding ore-forming fluids evolution through multi-stage scheelites: Insights from the first Neoproterozoic Jianzidong W deposit in the western Yangtze, South China - Zhongyuan Liu; Fuhao Xiong; Han Zhao; Jie Gan; Junqing Mu; Yu Gan; Hui Li; Yaming Tian; Hao Zou (Lithos, 2026)

Seasonal dynamics of microbial diversity and ecological functions in the river estuary area of Loushan River - Xin Hu; Chengci Liu; Jinhua Xu; Zhiyang Zhao; Hongyu Jin; Xiaodong Xu; Lu Qiao; Zhen Yang; Jincheng Li; Mutai Bao; Lei Huang; Yingchun Mu (Journal of Hydrology, 2026)

Root exudates drive metabolic remodeling of microbial and resistance to facilitate sulfonamide biodegradation in karst soil-carbonate rock interface - Yunping Zhao; Hui Mu; Bill X. Hu; Chuanshun Zhi; Hui Wang; Linxian Huang; Fen Huang; Kai Han (Journal of Hazardous Materials, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Mutant transcription factor CopR promotes LDB_RS05285 expression to suppress yogurt post-acidification and enhance texture stability - Wenhao Zhao; Xuemeng Fu; Dongyao Li; Qingqing Mu; Na Zhang; Yongsheng Sun; Miaoshu Wang; Hongtao Tian; Chen Li (Food Research International, 2026)

Structural modulation of casein peptide-hydroxytyrosol self-assembled nanocomplexes: Enhanced gastrointestinal stability and in vitro antioxidant activity - Si-Yi Han; Hong-Fu Zhao; Wen-Qi Liang; Ying-Hua Zhang; Zhi-Shen Mu (Food Research International, 2026)

Breast milk probiotic microbiota analysis identifies Lacticaseibacillus paracasei DPUMW-M14-9 with anti-inflammatory and barrier-protective functions: Functional and genomic characterization - Zhao Zhang; Yanchen Liu; Xuemei Zhu; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2026)

AE-TD3 with adaptive expert guidance: towards responsive deep reinforcement learning for building HVAC control systems - Zeqing Wu; Yunfei Mu; Xiaolong Jin; Yanze Xu; Hongjie Jia; Jun Zhao (Energy and Buildings, 2026)

Highly efficient Xe/Kr separation within a metal-organic framework featuring continuous molecule traps - Yan-Long Zhao; Xiang-Yu Li; Xuefeng Bai; Mu-Zi Li; Xin Zhang (Chemical Engineering Journal, 2026)

Elevational decline in soil bacterial diversity and its positive role in driving soil multifunctionality: a global meta-analysis - Manya Luo; Xia Jia; Yonghua Zhao; Kun Ren; Lei Zhang; Qi Mu; Shuyuan Yang (CATENA, 2026)

Thawing warm permafrost of quicklime (CaO) piles and their optimization design - Yuncheng Mao; Shanzhi Fan; Guoyu Li; Dun Chen; Changqing Zhao; Yanhu Mu; Haihong Zhang; Chunqing Li; Xiaosen Li; Xiaolin Li (Cold Regions Science and Technology, 2026)

Mechanistic insights into sulfidated nanoscale zero-valent iron enhanced methanogenesis: Electron redistribution and direct interspecies electron transfer-driven metabolic reconfiguration - Fangyuan Feng; Chunhui Zhao; Yinguang Chen; Yongfang Zhang; Xiaonong Hu; Hui Mu; Wen Zhang (Bioresource Technology, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Optimized Design and Experimental Evaluation of a Vibratory Screening Unit for Mactra veneriformis Harvesting on Intertidal Mudflats Based on the Discrete Element Method - Bin Xu; Shuyuan Liang; Yuzhong Lou; Jixuan Zhao; Hangqi Li; Yizhi Chang; Hao Wu; Guangcong Chen; Gang Mu (Fishes, 2025)
To enhance shell–mud separation and overall harvesting efficiency for Mactra veneriformis under intertidal mudflat conditions, a vibratory harvesting device driven by a crank–rocker mechanism that produces approximately rectilinear simple-harmonic motion was developed. Dynamic analysis of clam motion on the screen deck identified vibration amplitude, vibration frequency, excitation direction angle, and screen deck inclination angle as key determinants of screening performance. Single-factor tests, a Plackett–Burman design, a steepest-ascent experiment, and response surface methodology (RSM) optimization were conducted. Their influences on forward travel speed ranked as follows: screen deck inclination angle > excitation direction angle > vibration amplitude > vibration frequency. The optimized settings were vibration amplitude of 8.5 mm, excitation direction angle of 45°, screen deck inclination angle of 11°, and vibration frequency of 10 Hz. Intertidal mudflat trials yielded a harvesting efficiency of 342 kg/h and a clam breakage rate of 4.6%, meeting the design targets. After harvesting, the shear strength of the mudflat decreased, with disturbance mainly confined to the surface layer, thereby meeting the low-disturbance requirement and enabling ecologically friendly harvesting. These results provide a basis for the design and optimization of M. veneriformis harvesting machinery.

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Incorporating spatiotemporal structure to improve the understanding of Antarctic krill (Euphausia superba) distribution - Xiuxia Mu; Xinliang Wang; Chongliang Zhang; Xianyong Zhao; Jichang Zhang; Yunxia Zhao; Yiping Ying; Gangzhou Fan; Lu Liu; Jiancheng Zhu; Qingchang Xu (Fisheries Research, 2025)

Application of activated water irrigation technology: A sustainable way to improve soil fertility and crop adaptability in the sandy area of southern Xinjiang - Xiaoxian Duan; Quanjiu Wang; Weiyi Mu; Changkun Ma; Kai Wei; Yan Sun; Xue Zhao (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Global fixed-time singularity-avoidance cooperative formation control of underactuated unmanned surface vehicles via waypoints guidance: Theory and experiment - Zheng Wang; Yongsheng Zhao; Dongdong Mu; Xiao Liang; Yiqi Wang; Qian Wang (Ocean Engineering, 2025)

Refined evaluation of winter wheat drought and climate change implications - Junfang Zhao; Huiwen Peng; Yunkun Song; Jiaxin Wang; Jia Mu (Journal of Cleaner Production, 2025)

The distinct impact of nitrification inhibitors on ammonia-oxidizing prokaryotes: Growth, microbial community, and enzymatic mechanisms - Zimin Chai; Shishi He; Zhichao Tian; Guangli Mu; Yuanwei Li; Hongbin Mu; Zhirong Zhao; Maosheng Zheng (Journal of Environmental Chemical Engineering, 2025)

Construction of smartphone-assisted electrochemical molecularly imprinted sensor based on magnetic MOF@COF as a novel platform for portable and sensitive detection of staphylococcal enterotoxin B - Wei Hu; Minghao Ma; Bin Du; Yikan Zhao; Jiang Wang; Bing Liu; Xihui Mu; Zhangyan Hu; Zhihao Yi; Zhaoyang Tong (Journal of Environmental Chemical Engineering, 2025)

Development of a magnetite-oyster shell composite to improve methanogenesis in carbohydrate-rich wastewater treatment - Fangyuan Feng; Yichao Wang; Jingyang Luo; Chunhui Zhao; Yongfang Zhang; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Effects of roasting on the quality characteristics, sensory profiles, and volatile flavor compounds of different cuts of Yanbian yellow beef - Bowen Qin; Xiangji Meng; Rufeng Lian; Jinlong Tan; Chunxiang Piao; Juan Wang; Hongmei Li; Changcheng Zhao; Baide Mu; Guanhao Li (International Journal of Gastronomy and Food Science, 2025)

Post-synthetic acid treatment of aqueous synthesized bimetallic Ce/Zr MOF-801 enables efficient oxidative desulfurization of model fuels - Liang Chu; Zhaokun Wang; Zhaohui Liu; Teng Zhao; Liyan Wang; Mu Yang; Ge Wang (Fuel, 2025)

Comparison of compositional, structural, and functional characteristics in walnut (Juglans regia L.) proteins prepared from walnut meal: Effects of extraction and isolation methods - Yihan Mu; Xueying Song; Siliang Wu; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Chemistry, 2025)

Discontinuation of glacial meltwater input reshapes the diversity and stability of eukaryotic planktonic microbial communities in glacial lakes - Xiaodong Li; Qianggong Zhang; Peng Zhang; Qing Yang; Zijian Lu; Yanan Zhou; Meiqi Huang; Guangli Mu; Zhao Xue; Linyuan Lu; Yindong Tong (Environmental Research, 2025)

Experimental study on longitudinal shear resistance in composite frame beams under lateral loads - Mu-Xuan Tao; Tian-Shu Liu; Ji-Zhi Zhao (Engineering Structures, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Induced ethanol and higher alcohols formation during CO hydrogenation over a novel MoS2-MoO3 composite catalyst - Xiaomeng Yuwen; Xiaoliang Mu; Lu Zhao; Kegong Fang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Asymmetric actuators via lignin-cellulose nanofibrous composite films with programmable wet-light dual-responsiveness - Qiang Mu; Qiangli Zhao; Min Mao; Yao Liu; Jie Tao; Jiahao Kang; Wei Yong; Xinhai He; Jianhua Ma; Jianwei Li (Carbohydrate Polymers, 2025)

Spatio-temporal inversion of surface soil organic matter in the Hexi Corridor based on remote sensing data and multiple model integration - Lei Zhang; Xia Jia; Yonghua Zhao; Qi Mu; Lishan Shan; Ming Zhao; Shaocheng Si (CATENA, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Correction: Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

taVNS alleviates preeclampsia-induced vascular endothelial dysfunction via α7nAChR- IP3R1/GRP75/VDAC1 signal pathway - Jing Zhao; Yuman Lei; Chengcheng Mu; Yuwei Wu; Rourou Fang; Dongdong Wu; Shouzhu Xu; Haifa Qiao (Inflammation Research, 2025)

Transcriptome sequencing-based genetic diversity assessment of Lagenaria siceraria landraces using simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers - Saike Qi; Shan Liu; Bingbing Gao; Hongqiao Zhang; Ju Yang; Xiaodi Zhang; Li Geng; Yulu Gao; Wenchao Zhao; Hongmei Mu (Genetic Resources and Crop Evolution, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Splicing factor Nova regulates the splice variants in exons 3 and 6 of GABA receptor subunit RDL from Chilo suppressalis Walker (Lepidoptera: Crambidae) - Zijiao Song; Jie Jiang; Tao Tang; Guanghua Luo; Junyan Wang; Kaixiang Lin; Lili Mu; Chunqing Zhao (Pesticide Biochemistry and Physiology, 2025)

Hydrodynamic interference mechanism of ships in formation navigation - Dagang Zhao; Jinzhao Mu; Huawei Sun; Mingqi Bi; Xiangyu Liu (Ocean Engineering, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Reverse-tracing unravels microbial succession and flavor stratification driven by vertical physicochemical gradients in Zaopei fermentation - Boyang Xu; Shanshan Xu; Hao Zhou; Qinxiang Xu; Hui Zhang; Dongdong Mu; Xuefeng Wu; Eryong Zhao; Xingjiang Li (Food Chemistry, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Optimizing germination to enhance antioxidant and nutritional quality of sunflower seed oil: Role of phenylalanine ammonia-lyase - Zhang Lin; Ziyang Zhao; Zhenkang Yao; Lei Mu; Xiangyu Wang; Yuxuan Liu; Qi Li; Xiuzhu Yu (Food Chemistry, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Hierarchical solar interface evaporator derived from natural multilevel plant leaves for high-efficiency desalination - Jiujiu Tian; Xiaojiang Mu; Yitong Wang; Hailan Zhao; Lu Yin; Fan Zhang; Xiaoyang Wang; Lei Miao (Chemical Engineering Journal, 2025)

Plasmonic metamaterials with closed cells for infrared/visible compatible stealth - Zhiyu Ren; Tong Zhao; Sijia Niu; Wencheng Chen; Xiaoming Liu; Wangzhong Mu; Tie Liu; Qiang Wang (Chemical Engineering Journal, 2025)

Effect of mixing and compaction methods on the physical properties, strength and microstructure of phase change material-modified soils under freeze-thaw process - Jun Bi; Yuxuan Pan; Wenxuan Mu; Mingyi Zhang; Guiyu Zhao; Haoxin Chen; Pengfei Liu (Cold Regions Science and Technology, 2025)

Plant survival strategies under heterogeneous salt stress: remodeling of root architecture, ion dynamic balance, and coordination of metabolic homeostasis - Minghui Zhang; Menghan Pan; Hongjiao Li; Bingxiang Liu; Shenqi Qiao; ChangMing Ma; Hongxiang Mu; Wenhao Zhao; Jinyu Guo (Plant and Soil, 2025)

Rapid visual detection of Moniezia spp. in sheep feces via Recombinase Polymerase Amplification-Lateral Flow Dipstick (RPA-LFD) assay - Shaohua Zhang; Yeping Zhao; Weijia Liang; Shuai Wang; Xiu Cui; Haohan Zhu; Yueyue Zhang; Xiaolei Liu; Huimin Li; Wenjie Mu; Aijiang Guo (Veterinary Parasitology, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Transformation of chloroxylenol in real sewer sediments: Key adsorption sites and CYP450-catalyzed biodegradation - Xinhui Xia; Yujia Du; Huizhi Mu; Dan Li; Shuocheng Shao; Qingliang Zhao; Liangliang Wei (Journal of Hazardous Materials, 2025)

Laccase-mimicking chiral Cu-nanozymes for enantioselective catalysis of phenolic substrates - Qiaodan Du; Zhihao Mu; Dan Liang; Xinman Han; Yuan Zhao; Wei Ma (Journal of Hazardous Materials, 2025)

Oyster shell immobilized nano zero-valent iron for enhancing methane production from carbohydrate-rich food waste: Characterization, performance, and mechanism - Xiaofan Ding; Wei Jiang; Fangyuan Feng; Bochang Feng; Yanfei Li; Yongfang Zhang; Chuanshun Zhi; Chunhui Zhao; Jingyang Luo; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

Metabolites from Lactobacillus delbrueckii subsp. bulgaricus DLPU F-36 and L-Arginine promote immune tolerance to whey protein in rats by modulating Th1/Th2 and Th17/Treg balance - Zhao Zhang; Yanchen Liu; Yunpeng Xu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Intestinal metabolomic profiling provides insights into the molecular mechanisms for hyperuricemia-induced intestinal barrier dysfunctions in a hyperuricemia mouse model - Hailong Li; Qingli Zhang; Tingting Tang; Lei Zhu; Qu Chen; Haili Zhang; Yan Zhang; Zichu Zhao; Di Xiao; Xinlei Sha; Jingrong Mu; Jingjing Kong (Food and Chemical Toxicology, 2025)

Distribution patterns and assembly mechanisms of microbial communities in the riverine waters of southeastern Tibet - Yanhong Wang; Zhao Hao; Enyong Chen; Jianping Xu; Shuaishuai Huang; Qiong La; Pengxi Cao; Xiu Zhang; Junwei Wang; Nanmujia Pingcuo; Quzhen Baima; Jiawei Li; et al. (Environmental Research, 2025)

Diversification to extinction: oceanic and climatic context of the Ordovician - Mu Liu; Xiujuan Bao; David A.T. Harper; Thomas Algeo; Mingyu Zhao; Matthew Saltzman; Wang Zhang; Daizhao Chen; Shuai Yuan; Yihui Chen; Mengyu Wei; Junpeng Zhang; et al. (Earth-Science Reviews, 2025)

Cellulose-sponge hierarchical architecture-based ultra-high linearity flexible pressure sensor for magnitude and acting point detection - Shaowen Mu; Jianhong Hao; Yuqing Xia; Chenyang Hong; Jingxi Wang; Xincheng Tang; Ziqiang Wang; Xiaowen Zhu; Cancan Lv; Yunong Zhao; Siliang Wang; Xiaohui Guo (Chemical Engineering Journal, 2025)

High-performance flexible porous pressure sensor based on carbon nanocoils modified reduced graphene oxide - Chunhong Mu; Ying Zhou; Yingzi Gu; Shengzhe Zhao (Chemical Engineering Journal, 2025)

Corrigendum to “Study the photocatalytic mechanism of the novel Ag/p-Ag2O/n-BiVO4 plasmonic photocatalyst for the simultaneous removal of BPA and chromium(VI)” [Chem. Eng. J. 361 (2019) 1352–1362] - Wei Zhao; Jin Zhang; Fengxia Zhu; Feihu Mu; Lili Zhang; Benlin Dai; Jiming Xu; Anfeng Zhu; Cheng Sun; Dennis Y.C. Leung (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Identification and three-dimensional evolution characterization of long duration and high severity drought in Xinjiang based on precipitable water vapor - Shikang Zhao; Zhenxia Mu; Zilong Li; Rongqin Yang; Mianting Huang (Atmospheric Research, 2025)

Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

Hydroquinone Hydroxypropyl-β-cyclodextrin Inclusion Complex Based Topical Cream as an Effective Treatment of Melasma by Releasing Hydroquinone in a Controlled Manner - Yinling Mu; Hongbing Liu; Xianglin Guo; Yiyu Liu; Wanbing Pan; Fan Zhao; Haibing He; Jingxin Gou; Xing Tang; Tian Yin; Yu Zhang (Pharmaceutical Research, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Trend changes in tourism climate suitability in China and the impact of multiple atmospheric circulation patterns - Zikang Ren; Huarong Zhao; Xinzhi Mu; Kangming Shi; Xin Jin (International Journal of Biometeorology, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

The importance of fungal necromass in soil organic carbon: Insights from elevation gradients in arid regions - Mengfei Cong; Zhihao Zhang; Guangxing Zhao; Xinping Dong; Yan Lu; Lei Li; Yang Hu; Weiqi Wang; Zhaobin Mu; Akash Tariq; Jordi Sardans; Josep Peñuelas; et al. (Applied Soil Ecology, 2025)

Isotopic signaling and environmental significance of cave waters in a heavily rocky desertification area - Ju Ni; Yurong Mu; Dayun Zhu; Jialu Wang; Yurong Han; Yingshan Zhao; Ning Yang; Juanfang Du (Applied Geochemistry, 2025)

What does the dairy farming bring to the desertified soil? A case study - Zixi Han; Jianfei Zeng; Xu Zhao; Yanyan Dong; Yongsong Mu; Sha Wei; Yong Hou; Ziyu Han (Agricultural Systems, 2025)

Tissue-Selective Separation Mechanism of Multi-type Soft Tissues Under Waterjet Impact for Low-Trauma Cutting Surgery - Jiaqi Zhao; Xiao-Fei Song; Xiaoxian Wei; Jiuke Mu; Peng Peng; Wenli Yu (Annals of Biomedical Engineering, 2025)

High-Precision Small-Scale 3D Seismic Technology for Natural Gas Hydrate Exploration in the Northern South China Sea - Dasen Zhou; Siqing Liu; Xianjun Zeng; Limin Gou; Jing Li; Jingjing Zhang; Xiaozhu Hao; Qingxian Zhao; Qingwang Yao; Jiafa Zhang; Jiaqi Shen; Zelin Mu; et al. (Journal of Marine Science and Engineering, 2025)
To address the demand for high-precision exploration of natural gas hydrates in the northern South China Sea, this paper presents a novel high-precision small-scale 3D seismic exploration technology. The research team independently developed a seismic acquisition system, incorporating innovative designs such as a narrow trace spacing of 3.125 m and a short streamer length of 150 m. By integrating advanced processing techniques, including pre-stack noise suppression, spectral broadening, and refined velocity analysis, the system significantly enhances the precision and spatial resolution of shallow seismic data. During field trials in the Qiongdongnan basin, the system successfully acquired 3D seismic data over an area of 50 km2, enabling fine-scale imaging of sub-seabed strata within the upper 300 m. This represents a notable improvement in resolution compared to conventional 3D seismic technologies. When benchmarked against international counterparts such as P-cable, our system demonstrates distinct advantages in terms of exploration depth (reaching 1800 m) and dominant frequency range (spanning 10~390 Hz). The research findings provide a reliable technical approach for the detailed characterization of natural gas hydrates and the inversion of reservoir parameters, thereby holding significant practical value for advancing the industrial development of natural gas hydrates in China’s offshore areas.

Simulation analysis of mechanical response and failure mechanisms of maize stubble-soil composite based on discrete element method and fiber bundle model - Chunxiang Zhuo; Haiqing Tian; Ziqing Xiao; Qiaofei Mu; Leifeng Tang; Kai Zhao (Computers and Electronics in Agriculture, 2025)

A rapid calibration method for the discrete element model of straw fodder particle mixtures based on the UVE-PLS-GD algorithm - Ziqing Xiao; Haiqing Tian; Chunxiang Zhuo; Kai Zhao; Yang Yu; Qiaofei Mu; Xiaoyu Xue (Biosystems Engineering, 2025)

Corrigendum to “A novel indicator for assessing spatial coupling relationships within hybrid landscapes comprising diverse land cover types and its application to explaining urban thermal environment” [Sustainable Cities and Society 130 (2025) 106595] - Tao Mu; Ruting Zhao; Huawei Li; Yakai Lei; Qiuyuan Chen; Guohang Tian; Yali Zhang; Bo Mu (Sustainable Cities and Society, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Effects of metal oxides loaded with biochar on adsorption of cationic and anionic metals: A meta-analysis - Yang Yu; Xinwei Chen; Lingxin Zhao; Shufei He; Likui Feng; Weixin Zhao; Huizhi Mu; Qingliang Zhao; Liangliang Wei (Journal of Environmental Management, 2025)

Soybean protein isolate hydrolysate addition during fermentation of soybean meal with Aspergillus oryzae enhances the release of umami components in subsequent hydrolysis process - Yihan Mu; Hui Kang; Xueying Song; Chenchen Cao; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Bioscience, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Interlayer covalent bridging covalent organic polymers for highly efficient photocatalytic organic synthesis - Xia Zhao; Ai-Cen Li; Dan Yang; Yong-Hui Wang; Xin Mu; Cong Wang; Hua-Qiao Tan (Chemical Engineering Journal, 2025)

AC–DC electric field-induced microstructure arrangement in SiCw/SE composites for enhanced electro-thermal performance - Huanmin Yao; Haibao Mu; Wenrui Tian; Andrea Cavallini; Maoqun Shen; Wendong Li; Daning Zhang; Haoxiang Zhao; Guanjun Zhang (Chemical Engineering Journal, 2025)

Multi-crosslinked network enables robust cellulose/chitosan composite aerogel for triboelectric sensor with humidity adaptivity - Jiahao Kang; Qiangli Zhao; Min Mao; Yugen Wang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Numerical Simulation of CO2 Geological Storage and CH4 Replacement - Hongtao Mu; Shinian Li; Xiurong Wang; Xiaojing Zhao; Yankai Hou; Zhenli Luo; Le Fang (Pure and Applied Geophysics, 2025)

Full genome characterization of a novel zetapartitivirus infecting Alternaria tenuissima strain TY-26 associated with muskmelon leaf spot - Tongyu Mu; Xiaofan Sun; Wen Huang; Can Zhao; Xuehong Wu (Archives of Virology, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Defective hierarchical porous Ce-UiO-66 excites phosphotungstic acid for superior low-temperature oxidative desulfurization - Liang Chu; Zhaokun Wang; Teng Zhao; Mu Yang; Ge Wang (Journal of Hazardous Materials, 2025)

Screening of enzymes for bi-functional whey protein hydrolysates: virtual enzymolysis, fragmentomics, and molecular docking in silico - Ruoyun Gao; Fanhua Kong; Guangqing Mu; Xin Zhao; Jianbo Cheng; Fang Qian (Food Research International, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

Melatonin receptor–mediated signaling pathways drive time-dependent physiological recovery from freezing in Perccottus glenii - Zhaoyang Ning; Cunrun Ye; Yingqiao Chen; Jiajun Zhou; Xiaoyu Zhao; Ye Huang; Zhitao Liu; Weijie Mu (Fish Physiology and Biochemistry, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

A novel indicator for assessing spatial coupling relationships within hybrid landscapes comprising diverse land cover types and its application to explaining urban thermal environment - Tao Mu; Ruting Zhao; Huawei Li; Yakai Lei; Qiuyuan Chen; Guohang Tian; Yali Zhang; Bo Mu (Sustainable Cities and Society, 2025)

Determination of nitrofuran metabolites in fish samples by boronate affinity extraction coupled to HPLC-MS/MS using cis diol-modified mesoporous polymer (GMA-EGDMA) microspheres as adsorbents - Wendi Huo; Jincheng Li; Yupeng Wen; Xinyuan Zhang; Huan Liu; Yingchun Mu; Chunhui Zhao; Chaoying Zhang; Rongyue Zhang (Journal of Hazardous Materials, 2025)

Boron-induced phenylpropanoid metabolism, Na+/K+ homeostasis and antioxidant defense mechanisms in salt-stressed soybean seedlings - Mu Lu; Muhammad Riaz; Kaiqing Tong; Wenjing Hao; Yu Yang; Xiaomeng Zhao; Lu Wang; Yusheng Niu; Lei Yan (Journal of Hazardous Materials, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

A high-performance flexible coaxial BTO/PAN piezoelectric nanofibers for facial expression analysis - Junfei Lin; Junbin Yu; Fangyuan Chen; Xuying Jia; Jiahe Li; Juanhong Zhao; Jian He; Xiaojuan Hou; Jiliang Mu; Xiujian Chou (Chemical Engineering Journal, 2025)

Humidity-adaptive microcrystalline cellulose triboelectric composite film with engineered microstructures for sensing and energy harvesting - Min Mao; Qiangli Zhao; Jiahao Kang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Chemical homogeneity enables long-term stability of cobalt-free high-voltage spinel cathode materials - Chunlin Zeng; Guanjun Chen; Qian Zhang; Yan Li; Chengzhi Dai; Ruotong Zhao; Shichun Mu; Weihao Zeng; Jinlong Yang (Chemical Engineering Journal, 2025)

Long time-series change characteristics and suitable scale of oasis in arid and semi-arid regions of China - Lei Zhang; Xia Jia; Yonghua Zhao; Manya Luo; Qi Mu; Hongliang Kang; Peng Zhang (Applied Geography, 2025)

An Investigation Into the Long‐Chain Propagation Patterns and Driving Factors of Multiple Types of Droughts in Xinjiang - Shikang Zhao; Zhenxia Mu; Zilong Li; Xiaoyan Qiu; Jing Liu (International Journal of Climatology, 2025)
The process of drought propagation is extremely complex and involves all aspects of the water cycle. Clarifying the mechanism of drought propagation is of great significance for understanding the evolutionary pattern of drought and constructing a drought early warning system. However, due to the complexity of droughts and the numerous factors influencing them, there are certain limitations and shortcomings in studying the intrinsic links, propagation characteristics and triggering mechanisms of multiple drought types. To this end, this paper takes the Xinjiang region as the research object, identifies the drought events based on the run theory and determines the drought propagation time by matching the drought events; risk probabilities, trigger thresholds and drivers between different drought types were explored using copula functions, Bayesian theory and random forest models. The results show that (1) the average drought propagation time from meteorology to agriculture and from meteorology to hydrology in Xinjiang is 2.1 and 2.8 months, respectively. (2) The probability of the occurrence of agricultural (hydrological) drought increased with the severity of meteorological (agricultural) droughts. Specifically, the average probability of extreme meteorological (agricultural) droughts triggering mild agricultural (hydrological) droughts reached 89% (41%), with an average trigger threshold of −1 (−2.2). (3) Mild meteorological drought on the northern slopes of the Tianshan mountains was the primary trigger for mild agricultural drought, with an average trigger probability and threshold of 45% and −0.89, respectively. In contrast, moderate meteorological drought on the southern slopes of the Tianshan mountains was the main trigger for mild agricultural drought, with an average trigger probability and threshold of 56% and −1.1, respectively. (4) Meteorological drought triggers a significant reduction in the threshold for agricultural drought, mainly influenced by precipitation and potential evapotranspiration. Agricultural drought triggers a significant reduction in the threshold for hydrological drought, with temperature and potential evapotranspiration being the main drivers of the threshold change.

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Could chloroxylenol be used as WBE biomarker in gravity sewers? Fates, behaviors and feasible conditions - Xinhui Xia; Huizhi Mu; Yujia Du; Shuocheng Shao; Yaqun Li; Dan Li; Qingliang Zhao; Liangliang Wei (Water Research, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Green and sustainable strategy for separation and recovery of high-value fluorine and magnesium from fluorine slag by alkaline roasting-hydrometallurgy - Hang Zhao; Xiaoguang Zhang; Guosai Jiang; Feihua Yang; Yanling Wu; Panpan Mu; Haile Yan; De’an Pan (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical analysis and tracing of heavy metal contamination in groundwater using self-organizing mapping - Zhenzhou Sun; Qinghai Deng; Liping Zhang; Lusheng Song; Hongjuan Zhao; Jiutan Liu; Xiao Wu; Jiayi Mu (Environmental Geochemistry and Health, 2025)

How the Labor Mobility Impact Farmers’ Sustainable Livelihoods in Mountainous Regions: Evidence from Qinling-Daba Mountains, China - Huizhen Su; Xueyan Zhao; Fangfang Mu; Hainan Yang (Chinese Geographical Science, 2025)

Temporal transcriptome analysis provides molecular insights into night-time molting of juvenile mud crab (Scylla paramamosain) - Shujian Chen; Jiahao Liu; Ce Shi; Herve Migaud; Xuelin Zhao; Qingyang Wu; Yangfang Ye; Ronghua Li; Weiwei Song; Changkao Mu; Chunlin Wang (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Research on extraction of valuable metals from solid waste by deep eutectic solvents - A review - Chenye Yang; Jianying Zhao; Panpan Mu; Guosai Jiang; Zhe Tan; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Fixed-time fuzzy formation control for underactuated surface vehicles based on a novel trajectory-guiding strategy under model uncertainties - Zheng Wang; Yongsheng Zhao; Dongdong Mu; Xiaojie Sun; Yiqi Wang (Ocean Engineering, 2025)

PFASs contamination in the LongTing Lake sediments: Vertical-temporal variation, sources, microbial impacts, and risk assessment - Jingshen Zhang; Yang Liu; Yanghui Gong; Naying Wei; Zeyu Liu; Xiaohui Hou; Yue Mu; Xiaoli Zhao; Shengyong Jia; Fengchang Wu (Journal of Water Process Engineering, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Solar-driven evaporation based on regulation salt crystallization behavior for high-efficiency freshwater production and salt collection - Hailan Zhao; Xiaojiang Mu; Lu Yin; Zhixiang Zhang; Yang Long; Yitong Wang; Xiaoyang Wang; Jianhua Zhou; Lei Miao (Desalination, 2025)

Oral delivery of probiotic combined natural phenolic-metal framework with microencapsulation for prolonged intestinal retention and alleviation of inflammatory bowel disease - Mengna Zhao; Longkai Mu; Fangqin Xiang; Wenqing Lv; Haixin Jiang; Guanyu Tao; Bailiang Li (Chemical Engineering Journal, 2025)

Fabrication of a high strength, swelling resistance, and conductive hydrogel for flexible underwater sensor via ketalization - Kejun Zhong; Jie Xiang; Yu Liu; Chuanlin Song; Yuetong Mu; Ting Yao; Kai Zhao; Tianfeng Gu; Pengxiang Jia; Wenyan Zhang (Chemical Engineering Journal, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Effect of on stereoisomers of lactic acids on microbially-mediated reductive dissolution of clay minerals: Insights from DFT and experimental studies - Jingjie Yang; Liang Bian; Aiqin Wang; Xiaofeng Zhao; Jianan Nie; Temirlan Arslanov; Bin Mu; Hailiang Dong; Mianxin Song; Li Zeng; Peng Liu; Xiaobin Gu (Applied Clay Science, 2025)

Heading control of USV based on fractional-order model predictive control - Shiquan Zhao; Jingru Mu; Hongdan Liu; Yue Sun; Ricardo Cajo (Ocean Engineering, 2025)

Enhanced treatment efficiency of moxifloxacin-containing domestic wastewater in sequence batch reactors coupled with Spartina alterniflora biochar - Yuan-da Du; Yanan Gao; Mengyu Qin; Jian Liu; Shoubo Zhao; Haolin Mu; Xinru Lu; Shun Zheng; Xiaojing Chen; Zishu Wu; Qiang Kong; Jian Zhang (Journal of Water Process Engineering, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

Time-Series models for ground subsidence and heave over permafrost in InSAR Processing: A comprehensive assessment and new improvement - Chengyan Fan; Cuicui Mu; Lin Liu; Tingjun Zhang; Shichao Jia; Shengdi Wang; Wen Sun; Zhuoyi Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Diversity and dynamics of microbial communities during spontaneous fermentation of different cultivars of apples from China and their relationship with the volatile components in the cider - Jingyi Zhou; Xinyi Wang; Yonghao Cao; Yichao Cheng; Wenchao Li; Haibin Mu; Yanying Liang; Bin Tian; Xixi Zhao; Yuyang Song (Food Research International, 2025)

A double cross-linked film based on carboxymethyl chitosan binding with L-cysteine/ oxidized konjac glucomannan with slow-release of nisin for food preservation - Zihao Zhang; Lu Mu; Jinlong Li; Haixin Zhao; Hong-Man Hou; Gong-liang Zhang; Hongshun Hao; Jingran Bi (Food Chemistry, 2025)

Effects of different lactic acid bacteria on the physicochemical properties, functional characteristics and metabolic characteristics of fermented hawthorn juice - Maozhen Zhao; Yunjuan Mu; Zhiping Shi; Xueqi Wang; Wenhao Liu; Yuhan Zhou; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Chemistry, 2025)

Soil minerals regulate soil organic carbon accumulation through glomalin-related soil protein along an elevation gradient in a mountain arid ecosystem - Guangxing Zhao; Zhihao Zhang; Weiqi Wang; Mengfei Cong; Xinping Dong; Yanju Gao; Zhaobin Mu; Yan Lu; Lei Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Environmental Research, 2025)

An automatic arrival time picking algorithm of ultrasonic waves for concrete crack depth detection - Jintao Zhu; Weijie Li; Kaicheng Mu; Xue Zhang; Xuefeng Zhao (Engineering Structures, 2025)

Genesis, characteristic and disaster effects of loess meso-interfaces: A field geological investigation - Luqing Zhao; Penghui Ma; Jianbing Peng; Qingyi Mu; Yanqiu Leng; Xinghua Zhu; Zhijie Jia; Junyan Zhao; Zhiyuan He; Bingyao Huo; Zekun Li; Jingjing Nan (CATENA, 2025)

Single-chain variable fragment-based immunoassay for bioactive natural products - Xiping Cui; Jian Lu; Jinchao Wei; Suqing Zhao; Yiyong Yan; Guo Yin; Bing Wang; Yunping Mu; Peng Li (Phytochemistry Reviews, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from the phytopathogenic fungus Lasiodiplodia pseudotheobromae - Zhengzhe Guan; Mengjiao Wang; Jiayi Ma; Mengyuan Mu; Xinyu Li; Peimeng Sun; Mengyuan Zhang; Yuanyuan Zhang; Luyang Song; Caiyi Wen; Ying Zhao (Archives of Virology, 2025)

Astaxanthin ameliorates high-carbohydrate diet-induced ER stress, immunosuppression and hepatic glucose metabolism through AMPK/autophagy pathway in Channa argus - Mu-Yang Li; Yun-Zhuo Liu; Xiu-Mei Chen; Xiao-Tian Niu; Lu Chen; Lei Zhao; Gui-Qin Wang (Aquaculture, 2025)

Climate and biological factors jointly shape microbial community structure in the Yarlung Zangbo River during the dry season - Zhao Hao; Yanhong Wang; Enyong Chen; Xueyan Mu; Jiawei Li; Qiong La; Ji De; Yixuan Liu; Shuaishuai Huang; Weiguo Fang; Pengxi Cao; Junwei Wang; et al. (Science of The Total Environment, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Picoxystrobin causes mitochondrial dysfunction in earthworms by interfering with complex enzyme activity and binding to the electron carrier cytochrome c protein - Wentian Zhao; Kai Wang; Xiyan Mu; Jiazhen Jiang; Yang yang; Chengju Wang (Environmental Pollution, 2025)

Application of a thermo-mechanical-damage coupling model based on the TLF-SPH in the thermal cracking simulation of brittle solids - Dianrui Mu; Ke Zhang; Kesheng Jin; Shuai Zhao; Xiao Wang (Computers and Geotechnics, 2025)

Multiple-reprocessable guaiacol-derived epoxy vitrimer with disulfide crosslinks and closed-loop recycling of carbon fiber-reinforced composites - Kai Dong; Di Zhao; Yang Pang; Binghui Liu; Qian Liu; Tong Mu; Chengji Zhao (Chemical Engineering Journal, 2025)

Metabolic engineering of Escherichia coli BL21(DE3) cocultured with glucose and xylose for efficient production of 2′-fucosyllactose - Yunqi Zhu; Mingli Zhao; Hao Wang; Yingying Zhu; Wanmeng Mu (Bioresource Technology, 2025)

Numerical Simulation of Geothermal Extraction for Interaction between Irregular Curve Fractures and Heterogeneous Reservoirs - Shuxing Mu; Lianheng Zhao; Ao Zhang (Rock Mechanics and Rock Engineering, 2025)

TUBB4A Inhibits Glioma Development by Regulating ROS-PINK1/Parkin-Mitophagy Pathway - Xueru Xi; Suqin Chen; Xiaoli Zhao; Zimu Zhou; Shanjie Zhu; Xurui Ren; Xiaomei Wang; Jing Wu; Shuai Mu; Xianwen Li; Enfang Shan; Yan Cui (Molecular Neurobiology, 2025)

Carbon sink efficiency of Chinese mollusk mariculture - Lance Yu; Jianfeng Zhu; Xiaomu Guan; Lu Zhai; Zhuming Zhao; Yongtong Mu; Tao Liu (Aquaculture, 2025)

Upcycling acid waste gas containing H2S and CO2 into syngas and sulfur by non-thermal plasma coupled with Zn-Mo/Al2O3 catalyst - Wenshuang Feng; Xiaomeng Yuwen; Xiaoliang Mu; Lu Zhao; Kegong Fang (Fuel, 2025)

Optimizing β-Lactoglobulin antigenicity through single enzyme hydrolysis: Exploring structural changes and effects on linear epitopes - Peng Sun; Xiaomeng Wu; Qi Sun; Qing Zhao; Guangqing Mu; Fanhua Kong (Food Chemistry, 2025)

Urbanization exacerbates disparities in exposure to air pollution in China - Xiuling Zhao; Weiqi Zhou; Mu Hong; Andreas M. Neophytou (Environmental Research, 2025)

Dimeric PD-L1 specific affibody grafted Fe-based nanosheets for tumor-targeting dual-mode magnet resonance imaging and enhancement of Photothermal-Immunotherapy - Xinyu Zhang; Hui Liu; Chenyu Wang; Yuan Gao; Shiqi Zhao; Mengyao Mu; Ke Ren; Yufang Gong; Qing Fan; Xiao Sun (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Comparing on-line continuous movement decoding with joints unconstrained and constrained based on a generic musculoskeletal model - Lizhi Pan; Zhongyi Ding; Haifeng Zhao; Ruinan Mu; Jianmin Li (Medical & Biological Engineering & Computing, 2025)

Changes in River Cross-section Morphology and Response to Streamflow and Sediment Processes in Middle Reaches of Yellow River, China - Yongfu Wen; Pengfei Li; Mengzhen Li; Chaohui Ma; Peng Gao; Xingmin Mu; Guangju Zhao (Chinese Geographical Science, 2025)

Zinc Transporter 9 (ZnT9) Improves Obesity-Induced Asthenospermia by Attenuating Endoplasmic Reticulum Stress (ERS) - Chen Liang; Mingyang Chen; Zhidan Mu; Xinyan Tian; Wenzhen Zhao; Yarong Hu; Juan Su (Biological Trace Element Research, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

A comprehensive study on fermentation and aroma contributions of Torulaspora delbrueckii in diverse wine varieties: Insights from pure and co-fermentation studies - Yichao Cheng; Shijin Geng; Jin Zhang; Xixi Zhao; Jiao Jiang; Yanying Liang; Haibin Mu; Wenchao Li; Yi Qin; Yanlin Liu; Yuyang Song (Food Research International, 2025)

Changes in volatile flavors during the fermentation of tomato (Solanum lycopersicum L.) juice and its storage stabilization - Aihemaitijiang Aihaiti; Lei Zhao; Ruxianguli Maimaitiyiming; Liang Wang; Ruoqing Liu; Ying Mu; Keping Chen; Yu Wang (Food Chemistry, 2025)

Influences of freeze-thaw cycles on desiccation cracking of an intact loess - Luqing Zhao; Penghui Ma; Qingyi Mu; Zhijie Jia; Junyan Zhao; Zhiyuan He; Bingyao Huo; Zekun Li; Jianbing Peng (Engineering Geology, 2025)

Scalable, flexible and hierarchically porous Janus membrane inducing Zn-Ion flux redistribution and desolvation for dendrite-free zinc anodes - Jiawei Mu; Miao Yu; Bo Zhao; Yan Dai; Tiantian Li; Xiangcun Li; Xinhong Qi; Xuri Wang; Gaohong He (Chemical Engineering Journal, 2025)

Single-atom nanozyme immunoassay with electron-rich property for clinical patient cancer detection - Qingshan Liu; Guo Li; Yang Cao; Yaoyao Ren; Qiong Qin; Lei Li; Hao Zhang; Qi Xin; Xiaoqun Gong; Lingyu Zhao; Shu Zhang; Yonghui Li; et al. (Chemical Engineering Journal, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

High-performance biomass moisture-electric generators derived from Distillers’ spent grains: Synthesis, photothermal enhancement, and environmental sensing applications - Haichuan Gao; Zihao Feng; Wenjun Li; Jiatian Zhu; Shengdong Mu; Hongkai Zhang; Genqiao Liu; Wei Zhao; Bailiang Xue; Yonghao Ni (Chemical Engineering Journal, 2025)

Environmental behavior, toxic potencies, and risks of liquid crystal monomers: A critical review - Jiawei Cheng; Xiaojuan Li; Yawen Yuan; Mengxiao Wang; Yunsong Mu; Xiaoli Zhao; Fengchang Wu; John P. Giesy (Critical Reviews in Environmental Science and Technology, 2024)

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Stochastic processes driving cyanobacterial temporal succession in response to typhoons in a coastal reservoir - Yajun Wang; Tianzheng Cao; Qingqing Liu; Boyu Xuan; Zhengyuan Mu; Jian Zhao (Water Research, 2024)

Preparation of agriculture film from cow manure for silage maize planting: Experimental study and life cycle assessment - Zixi Han; Xu Zhao; Bingxin Tong; Yongsong Mu; Xiangjun Yang; Yong Hou; Zhiping Zhu (Waste Management, 2024)

Phytocannabinoid-like meroterpenoids from twigs and leaves of Rhododendron spinuliferum - E-E Luo; Wu-Fen Yang; Zhao-Jie Wang; Ling-Yun Chen; Mu-Yuan Yu; Xiao-Dong Luo; Xu-Jie Qin (Phytochemistry, 2024)

Research on the pitch angle attitude control of underwater vehicles based on a novel butterfly-shaped blocks structure - Yanhu Chen; Xinyu Fei; Xiutong Mu; Xiaoyan Zhao; Suohang Zhang; Canjun Yang (Ocean Engineering, 2024)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Role and mechanism of the outer membrane porin LamB in T-2 mycotoxin-mediated extensive drug resistance in Escherichia coli - Fengru Deng; Li Zhao; Ping Wei; Enhua Mai; Meichan Chen; Huixin Yang; Peiqiang Mu; Jun Wu; Jikai Wen; Yiqun Deng (Journal of Hazardous Materials, 2024)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

Variations of soil infiltration in response to vegetation restoration and its influencing factors on the Loess Plateau - Shuyu Zhang; Guangju Zhao; Junjian Fan; Mingyue Yang; Peng Tian; Xingmin Mu; Ren Geng (Journal of Environmental Management, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Net primary productivity of paleo-peatlands linked to deep-time glacial periods in the late Carboniferous and early Permian icehouse interval - Yanwen Shao; Fenghua Zhao; Baruch Spiro; Dehui Li; Guangyuan Mu; Jiangman Chu; Jing Lu; Longyi Shao (International Journal of Coal Geology, 2024)

Regulation mechanisms of allergenic epitope sites in casein by microbial and plant-derived proteases - Qi Sun; Guangqing Mu; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong (Food Bioscience, 2024)

Rational modification of Neisseria meningitidis β1,3-N-acetylglucosaminyltransferase for lacto-N-neotetraose synthesis with reduced long-chain derivatives - Mengting Tao; Longhao Yang; Chunhua Zhao; Zhaolin Huang; Mingli Zhao; Wenli Zhang; Yingying Zhu; Wanmeng Mu (Carbohydrate Polymers, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

An extension to ensemble forecast of conditional nonlinear optimal perturbation considering nonlinear interaction between initial and model parametric uncertainties - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Xing-Rong Chen; Bo Qin; Guo-Kun Dai (Atmospheric Research, 2024)

Characterization of a novel heterozygous frameshift variant in NDP gene that causes familial exudative vitreoretinopathy in female patients - Mu Yang; Li Peng; Liting Lv; Erkuan Dai; Yunqi He; Rulian Zhao; Shujin Li (Molecular Genetics and Genomics, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Synthesis of bioactive oligosaccharides and their potential health benefits - Yihan Chen; Yuxi Wen; Yingying Zhu; Zhengxin Chen; Wanmeng Mu; Chao Zhao (Critical Reviews in Food Science and Nutrition, 2024)

Which emerging micropollutants deserve more attention in wastewater in the post-COVID-19 pandemic period? Based on distribution, risk, and exposure analysis - Xinhui Xia; Huizhi Mu; Yaqun Li; Yanlong Hou; Jianju Li; Zixuan Zhao; Qingliang Zhao; Shijie You; Liangliang Wei (Science of The Total Environment, 2024)

Improvement of model simulation for summer PM2.5 and O3 through coupling with two new potential HONO sources in the North China Plain - Xiaoxi Zhao; Min Song; Xiujuan Zhao; Chaoyang Xue; Pengfei Liu; Can Ye; Xiaowei He; Yujing Mu; Bo Hu (Science of The Total Environment, 2024)

Downward shortwave radiation modeling over rugged terrain with clouds - Guangjian Yan; Chunqiang Zhao; Qing Chu; Xihan Mu; Yingji Zhou; Yanan Liu; Xuejun Wang; Donghui Xie (Remote Sensing of Environment, 2024)

Study on the shielding of harmful components in spent FCC catalyst tailings - Haojie Zhang; Jianying Zhao; Panpan Mu; Xiaoguang Zhang; Shaogang Zhang; De’an Pan (Process Safety and Environmental Protection, 2024)

Biocontrol efficacy and mechanism of endophytic Bacillus velezensis HE-23 from Aucklandia lappa roots against the gray mold of postharvest tomato - Wei Jian; Yu Chen; Shiyu Liu; Xiaogang Ou; Lixinyu Sun; Huiming Gong; Qiutong Mu; Zhengguo Li; Zhengwu Zhao (Postharvest Biology and Technology, 2024)

Effects of two types of corn starches on physicochemical and structural properties of red bean protein isolate acid-induced cold gels - Qi Qi; Yanfei Mu; Yifan Li; Fang Wang; Yuxuan Mao; Xinqi Li; Xiaopian Yan; Jinying Li; Chengbin Zhao; Jingsheng Liu (Journal of Food Engineering, 2024)

Investigating the effects of low-salt processing on the umami peptides of dry-cured ham using peptidomics techniques - Ming Ju; Mingxun Cui; Chunxiang Piao; Baide Mu; Jian Zhang; Lujuan Xing; Changcheng Zhao; Guanhao Li; Wangang Zhang (Food Chemistry, 2024)

Permeability characteristics, structural failure characteristics, and triggering process of loess landslides in two typical strata structures - Zekun Li; Penghui Ma; Jianqi Zhuang; Qingyi Mu; Jiaxu Kong; Luqing Zhao; Jianbing Peng (Engineering Geology, 2024)

Orthogonal photochemistry toward spatial reprogramming of 3D-printed liquid crystal elastomers - Hong Wan; Guancong Chen; Xiaorui Zhou; Hongfeng Mu; Chen Yang; Di Chen; Chujun Ni; Zizheng Fang; Qian Zhao; Tao Xie; Ning Zheng (Chemical Engineering Journal, 2024)

Bis-cationic crosslinked anion exchange membranes based on carbazole-containing polyaromatics with excellent ionic conductivity for alkaline water electrolysis - Yang Pang; Qijia Li; Binghui Liu; Qian Liu; Tong Mu; Yuetong Gao; Chengji Zhao (Chemical Engineering Journal, 2024)

Seasonal simulation and source apportionment of SO42− with integration of major highlighted chemical pathways in WRF-Chem model in the NCP - Xiaoxi Zhao; Xiujuan Zhao; Dan Chen; Jing Xu; Yujing Mu; Bo Hu (Atmospheric Pollution Research, 2024)

Phenotypic characterization and genetic mapping of the semi-dwarf mutant sdw9 in maize - Jiawen Zhao; Baiyu Yuan; Hao Zhang; Xiao Guo; Liangfa Wang; Xiaoqian Qiu; QianKun Xie; Liqin Mu; Chenhui Ma; Teng Zhou; Javed Hussain; Xiaoyang Chen; et al. (Theoretical and Applied Genetics, 2024)

Spatial variations of the relationships between bacterial diversity and forest ecosystem multifunctionality in the Qinling Mountains, China - Manya Luo; Xia Jia; Yonghua Zhao; Xuan Ye; Kun Ren; Qi Mu; Shuaizhi Kang; Huanyuan Wang; Juan Li (Applied Soil Ecology, 2024)

Facing the solid waste of cotton straw and plastic mulch film mixture in China: Centralized or decentralized pyrolysis facility? - Hao Zhang; Peng Jiang; Guanhan Zhao; Lin Li; Minjiao Chen; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Waste Management, 2024)

Involvement of Hg-bearing methane seeps in forming Ediacaran cap carbonate in South China - Xiaodie Mu; Xiangdong Wang; Zhongwu Lan; He Zhao; Zhong-Qiang Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Gasification performance of wet hydrochar from co-hydrothermal carbonization of high-moisture sludge and fungus bran - Shuai Guo; Jiyou Mu; Deng Zhao; Hongwei Qu; Baizhong Sun; Xingcan Li; Li Yang (Journal of Environmental Chemical Engineering, 2024)

A critical review on the activation of peroxymonosulfate by MOFs for antibiotics degradation: Affecting factor, performance and mechanism - Yiyun Li; Chunhui Zhang; Guifeng Zhao; Zhao Zhang; Peidong Su; Yanxin Li; Yonglin Mu; Weilong Zhou (Journal of Environmental Chemical Engineering, 2024)

Coal-based graphene formation by CO2 laser scribing: Various structures and excellent electrochemical performance - Yungang Zhao; Shaoqing Wang; Xiaoling Wang; Lu Zhang; Jidun Sha; Xiaomei Zhang; Ruifeng Mu; Zeyu Dong (Fuel, 2024)

Characterization of SCOBY-fermented kombucha from different regions and its effect on improving blood glucose - Yang Meng; Xueqi Wang; Yunjuan Mu; Maozhen Zhao; Yujia Liu; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Bioscience, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Monovalent cation exchange membranes prepared by Fe3+-assisted coupled surface modification of PEI-PPy for potassium extraction from simulated brine - Mengmeng Sun; Chenglin Mu; Shuo Wang; Jingtao Bi; Xiaofu Guo; Shizhao Wang; Yingying Zhao (Desalination, 2024)

Long-term storage and intradermal vaccination of tumor-derived exosomes via sugar microneedles for improving tumor immunotherapies - Sijia Mu; Tingting Qian; Zhiming Li; Puxuan Zhao; Yanxin Tao; Hao Chang; Fengli Qu (Chemical Engineering Journal, 2024)

Multifunctional ultraelastic helical conductive yarn for motion detection and human-machine interaction - Tonghua Bai; Yaqiong Wang; Keping Zhu; Xuefeng Zhang; Yue Mu; Jingchong Liu; Guichu Yue; Zhimin Cui; Nü Wang; Jie Bai; Yong Zhao (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Study on water-salt phase transition of saline soils during freezing - Fengxi Zhou; Wencang Zhao; Zhanlin Mu; Yuhong Yang; Xusheng Wan (Cold Regions Science and Technology, 2024)

Effects of a Chinese herbal medicine mixture on growth performance, immune response, and gene expression in Chinese soft-shelled turtles (Pelodiscus sinensis) - Mengyan Lan; Yaguang Wang; Yuqi Mu; Yali Li; Zhao Zhang; Yueqiang Guan (Animal Feed Science and Technology, 2024)

Research on Influencing Factors of Cable Clamp Bolt Elastic Interaction in Cross-Ocean Suspension Bridges - Fengrui Mu; Bo Wang; Yongjun Zhou; Yuan Jing; Yu Zhao; Zhiran Luo (Journal of Marine Science and Engineering, 2024)
Suspension bridges are the most common type of bridge used to cross the ocean. The cable clamps in suspension bridges clamp the main cables by bolt preload, but the elastic interaction of the bolts reduces the preload, which is detrimental to the force in suspension bridges. However, research on the factors influencing the elastic interaction of cable clamp bolts in suspension bridges is currently limited. This paper aims to explore the law of influence of external factors on the elastic interaction of bolts through a combined approach of theoretical analysis, full-scale experiment, and finite element simulation. The results indicate that the average preload loss was reduced by about 27% when the elastic modulus was increased by about 110%. The average preload loss was reduced by about 45% when the bolt center distance was increased by 75%. The number of bolts has a small effect on the elastic interaction, which can be ignored. When the preload of bolt installation was increased by 133%, the average preload loss was reduced by approximately 125%, which was almost a linear relationship. Tightening the bolt from the center bolt creates greater elastic interaction. The conclusions can provide suggestions for reducing the elastic interaction of bolts in the design and construction of suspension bridge cable clamps.

An accurate handheld device to measure log diameter and volume using machine vision technique - Min Xu; Shuai Chen; Shoushuai Xu; Baoyan Mu; Yue Ma; Jinghui Wu; Yue Zhao (Computers and Electronics in Agriculture, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Effect and application of spray drying and freeze drying on characterization of walnut oil microcapsules - Mingming Wang; Hongyu Mu; Lei Peng; Chunlei Tan; Yinyan Chen; Jun Sheng; Yang Tian; Cunchao Zhao (Journal of Food Engineering, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Comprehensive insights into the impact of magnetic biochar on protein hydrolysis in sludge anaerobic digestion: Protein structures, microbial activities and syntrophic metabolisms - Likui Feng; Huizhi Mu; Zhelu Gao; Tianyi Hu; Shufei He; Yu Liu; Shijie You; Qingliang Zhao; Liangliang Wei (Water Research, 2024)

Neoproterozoic tungsten mineralization and associated granitic magmatism in the western Yangtze Block, South China: Mineralization age, petrogenesis and geodynamic implications - Zhongyuan Liu; Fuhao Xiong; Hui Li; Han Zhao; Tingting Gong; Jie Gan; Junqing Mu; Xiaohui Zeng (Precambrian Research, 2024)

A comparative well-to-wheel analysis of renewable energy pathways for hydrogen and battery electric vehicles - Fanlong Bai; Fuquan Zhao; Xinglong Liu; Zhexuan Mu; Han Hao; Zongwei Liu (Journal of Cleaner Production, 2024)

Hydrothermal-assisted acid-etching of oil shale semi-coke for preparation of mineral/biochar nanocomposites and selective adsorption toward mycotoxins - Feng Zhao; Bin Mu; Yuru Kang; Dandan Wang; Gong Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2024)

Bio-fuel production from hydroconversion of hexadecane over Pt/SAPO-11 catalysts - Chao Mu; Junhao Sun; Chen Xie; Jing Xu; Jinxuan Bao; Haozhe Zhang; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2024)

Structural, physicochemical and digestive properties of non-covalent and covalent complexes of ultrasound treated soybean protein isolate with soybean isoflavone - Fang Wang; Jinying Li; Qi Qi; Yuxuan Mao; Xiaopian Yan; Xinqi Li; Yanfei Mu; Hao Zhang; Chengbin Zhao; Jingsheng Liu (Food Research International, 2024)

Combining lipase enzymatic techniques and antioxidants on the flavor of structured lipids (SLs) prepared from goat butter and coconut oil - Weihao Mu; Ying Zhao; Zhuo Wang; Yajun He; Chen Yang; Jianming Wang (Food Bioscience, 2024)

Exploring Cr(VI)-induced blood-brain barrier injury and neurotoxicity in zebrafish and snakehead fish, and inhibiting toxic effects of astaxanthin - Mu-Yang Li; Yan-Chao Shi; Wan-Xin Xu; Lei Zhao; Ai-Zhong Zhang (Environmental Pollution, 2024)

Vertical transmission of aerosols between building flats through drainage system: A review - Min Chang; Di Mu; Yi Zhao; Lingjun Xiao; Yan Wu; Naiping Gao (Building and Environment, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

An edge feature-based external calibration of monocular camera and LiDAR using in-orbit data - Jiaqian Hu; Bin Song; Jinzhen Mu; Hanxue Zhao; Shuang Li (Advances in Space Research, 2024)

A critical review on antibiotics removal by persulfate-based oxidation: Activation methods, catalysts, oxidative species, and degradation routes - Yanxin Li; Chunhui Zhang; Guifeng Zhao; Peidong Su; Jianbing Wang; Yiyun Li; Weilong Zhou; Yonglin Mu; Junke Zhang; Wenzong Liu (Process Safety and Environmental Protection, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Inclined solar interface evaporation system with downward steam generation for efficient desalination and salt crystallization positioning - Mengnan Qu; Yue Zhao; Jiehui Li; Jufeng Yan; Leihuan Mu; Qinghua Liu; Yuyu Xue; Cai-li Sun; Nan Zhang; Jinmei He (Desalination, 2024)

A gas-mechanical-damage coupling model based on the TLF-SPH method and its application to gas seepage in fractured coal - Dianrui Mu; Qing Ma; Ke Zhang; Jiyuan Zhao (Computers and Geotechnics, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Spatiotemporal variations of extreme weather events and climate drivers in the Three Gorges Reservoir Area and its surrounding regions from 1960 to 2020 - Zikang Ren; Huarong Zhao; Xinzhi Mu; Qinxue Xu; Kangming Shi; Guoliang Yang (Atmospheric Research, 2024)

Synergistic developmental effects of zebrafish exposed to combined perfluorooctanoic acid and atrazine - Xiaoyu Zhao; Beinan Wang; Xiao Song; Linjuan He; Wei Zhang; Yongzhong Qian; Xiyan Mu; Jing Qiu (Chemosphere, 2024)

Understanding the shift in drivers of terrestrial water storage decline in the central Inner Mongolian steppe over the past two decades - Xiao Zhang; Xiong Wu; Wenping Mu; Rong Zhao; Baoying Ye; Zhongke Bai (Journal of Hydrology, 2024)

Experimental investigation on the depressurization-assisted CH4/CO2 replacement behavior in the muddy silt slurries - Liang Mu; Huixing Zhao; Xianlong Li; Jiguang Zeng; Qingyan Cui (Gas Science and Engineering, 2024)

Effects of Lacticaseibacillus paracasei XJ-003 on the allergenicity and antigenicity of milk proteins during fermentation - Yunpeng Xu; Feifei Zhang; Ruida Ma; Zhao Zhang; Lei Chi; Yue Li; Chao Xu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2024)

Fermented bile acids improved growth performance and intestinal health by altering metabolic profiles and intestinal microbiome in Micropterus salmoides - Qing Guo; Wenwen Liu; Lu Zhao; Yiming Sui; Houfa Zhao; Yining Liu; Cuimin Mu; Xuepeng Wang (Fish & Shellfish Immunology, 2024)

Effects of eutrophication on the horizontal transfer of antibiotic resistance genes in microalgal-bacterial symbiotic systems - Ziqi You; Ce Wang; Xiaobin Yang; Zikuo Liu; Yueqiang Guan; Jiandong Mu; Huijuan Shi; Zhao Zhao (Environmental Research, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Developing intelligent Earth System Models: An AI framework for replacing sub-modules based on incremental learning and its application - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Bo Qin; Guo-Kun Dai; Guan-Bo Zhou (Atmospheric Research, 2024)

Variation of enzymes activities in haemocytes and serum of honeysuckle geometrid, Heterolocha jinyinhuaphaga Chu (Lepidoptera: Geometridae) larvae infected by Escherichia coli - Yu-yong Xiang; Xiu-jie Mu; Yan Zhao (International Journal of Tropical Insect Science, 2024)

Formation Mechanism of NW-Trending Faults and Their Significance on Basin Evolution in Zhu III Depression of the Pearl River Mouth Basin, SE China - Pengfei Zhu; Lintao Zhao; Jiantai Zhang; Dunling Mu; Yichun Chen; Pengfei Rong (Journal of Marine Science and Engineering, 2024)
The Zhu III Depression, situated in the northern Pearl River Mouth Basin, features a complex fault system composed of NE–SW-, nearly E–W-, and NW–SE-oriented faults. However, there is limited research on NW-trending faults, especially regarding their formation mechanisms. Through structural analysis of 3D seismic profiles, we have revealed the geometric and kinematic characteristics of NW-trending faults and categorized them into three types based on their formation mechanisms: extensional fault, dextral transtensional fault, and sinistral strike–slip fault. The extensional faults predominantly developed as boundary faults during the rifting I period, caused by tectonic inversion of the NW–NWW-trending basement faults since early Eocene. The transtensional fault resulted from the dextral strike–slip motion of the NE-trending basin-controlling faults since late Eocene, under the regional dextral extension stress setting. The sinistral strike–slip faults have been dominant during the post-rifting period since early Oligocene. This is due to the sinistral shearing action related to the southeastward lateral extrusion of the Indochina Block and slab pull southward by subduction of the proto-SCS. The NW-trending faults controlled the development of local tectonics and structures, the depocenter migration during the rifting period, and the trapping, migration, and preservation of oil and gas.

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

In-situ curing poly(N,N'-Methylenebisacrylamide)-based composite electrolyte reinforced with high-strength glass fiber skeleton for solid state lithium ion batteries - Yuxiang Zhang; Shijie Lu; Zhikun Zhao; Xinyu Zhang; Haijian Lv; Zhuolin Yang; Wenbin Sun; Man Xie; Daobin Mu (Chemical Engineering Journal, 2024)

Effect of Maillard reaction based on catechol polymerization on the conversion of food waste to humus - Daichen Mu; Chao Wang; Xinyu Geng; Yue Zhao; Taha Ahmed Mohamed; Di Wu; Zimin Wei (Chemosphere, 2024)

The major role of glucocorticoid receptor (GR) in astaxanthin alleviates immune stress in Channa argus lymphocyte - Xiao-Tian Niu; Chuang Sun; Lei Zhao; Xiu-Mei Chen; Gui-Qin Wang; Mu-Yang Li (Aquaculture, 2024)

Performance of microbial inoculation and tricalcium phosphate on nitrogen retention and conversion: Core microorganisms and enzyme activity during kitchen waste composting - Taha Ahmed Mohamed; Zimin Wei; Mohamed Mohaseb; Wu Junqiu; Taha El Maghraby; Xiaomeng Chen; Yousif Abdelrahman Yousif Abdellah; Daichen Mu; Mohamed El Kholy; Chaonan Pan; Ayodeji Bello; Guangren Zheng; et al. (Journal of Environmental Management, 2024)

Isolation and identification of novel umami-enhancing peptides from fermented soybean meal hydrolysate by consecutive chromatography and UPLC–ESI–QTOF–MS/MS - Chenchen Cao; Hui Kang; Yihan Mu; Jianan Zhang; Weizheng Sun; Mouming Zhao; Guowan Su (Food Bioscience, 2024)

Adsorption of humic acid from different organic solid waste compost to phenanthrene, is fluorescence excitation or quenching? - Xinya Su; Ruju Zhang; Huan Cao; Daichen Mu; Liqin Wang; Caihong Song; Zimin Wei; Yue Zhao (Environmental Pollution, 2024)

Association between PM10 pollution and the hospitalization of chronic obstructive pulmonary disease with comorbidity: evidence in 17 cities of Henan, Central China - Yanran Duan; Hang Fu; Shuai Jiang; Zhao Yin; Sufan Wang; Jinghong Gao; Mengyu Yang; Suxian Wang; Zihan Mu; Changying Chen; Yaojun Zhao; Chengzeng Wang (International Journal of Biometeorology, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Repeat dose and reproductive toxicity of thrombopoietin mimic peptide in Sprague-Dawley rats - Shidong Qiu; Yuji Liang; Xiaobo Wang; Xiue Li; Guoyue Wei; Peng Xiao; Suling Teng; Peilu Sun; Lei Song; Zenglin Zhao; Yanling Mu (Regulatory Toxicology and Pharmacology, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

Facile method constructed naphthalene and Cu-C/Ni-C modified amorphous boron with high ignition and combustion performances - Taizhong Huang; Siyu Xu; Heng Li; Hanyu Jiang; Yanlu Mu; Ergang Yao; Xinyu Zhu; Fengqi Zhao (Chemical Engineering Journal, 2024)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Complete genome sequence of a novel partitivirus with a dsRNA3 segment, isolated from Fusarium commune strain CP-SX-3 causing strawberry root rot - Yumeng Zhao; Xinyi Zhang; Tongyu Mu; Xuehong Wu (Archives of Virology, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Revealing the release and migration mechanism of heavy metals in typical carbonate tailings, East China - Rong Zhao; Xiong Wu; Ge Zhu; Xiao Zhang; Fei Liu; Wenping Mu (Journal of Hazardous Materials, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Screening of anti-allergic Lactiplantibacillus species by splenocyte sensitization model and evaluate their probiotic and postbiotic characteristics - Lu Feng; Zihao Guo; Jinghong Zhao; Wenpu Yao; Xinling Li; Linying Wu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2024)

Variation of runoff-sediment relationship at flood event scale in three typical watersheds of the Loess Plateau - Ren Geng; Zixuan Ye; Peng Tian; Qiu Jin; Bo Bi; Guangju Zhao; Xingmin Mu; Tongshun Wang; Dadong Zhu (CATENA, 2024)

BioTreasury: a community-based repository enabling indexing and rating of bioinformatics tools - Qi Zhao; Xin Zhou; Jingxing Wu; Jieyi Cai; Xiaoqiong Bao; Lin Tang; Chaoye Wang; Chunlei Liu; Yukai Wang; Yuyan Teng; Mohan Zheng; Weiping Mu; et al. (Science China Life Sciences, 2024)

Assessment of annual variability in the population status and reproductive cycle of purple sea urchins (Heliocidaris crassispina, Agassiz, 1864) in Daya Bay, China - Xinye Zhao; Xiaohui Mu; Yu Guo; Jiayang Li; Zhenhua Ma; Gang Yu; Chuanxin Qin (Frontiers in Marine Science, 2024)
The purple sea urchin ( Heliocidaris crassispina ) is one of the main drivers of ecosystem dynamics, and its reproductive cycle plays an important role in population structure and size variability. In this study, we analyzed the population structure, gonadal developmental characteristics, reproductive cycle and other factors influencing wild purple sea urchins from December 2021 to November 2022 in Daya Bay, Guangdong, China. The results showed that purple sea urchins showed an allometric growth pattern, there were obvious seasonal variations in the population size, and fishing pressure reduced the sea urchin populations; two-factor analysis of variance (ANOVA) and correlation analyses showed negative correlations between month (M), test diameter (TD), weight (W) and gonadal index (GI) ( P > 0.01), and a positive correlation between TD, weight (W), and GI ( P <0.01); the gonadal development process can be divided into recovery, growth, prematuration, maturation, and late discharge, with almost synchronous development of male and female gametes; the spawning period is from April to November, which is longer than in the temperate zones, showing two spawning peaks in April and August. The time of spawning is influenced by temperature and food. Data on the breeding cycle of sea urchins in Daya Bay were obtained in this study. This information can offer theoretical assistance in the preservation and management of both artificial nurseries and wild resources.

Physiological characteristics, rhizosphere soil properties, and root-related microbial communities of Trifolium repens L. in response to Pb toxicity - Meiqi Mu; Zicheng Wang; Zirui Chen; Yuchen Wu; Wanting Nie; Siwen Zhao; Xiujie Yin; Xiaohua Teng (Science of The Total Environment, 2024)

Effects of bubble and reactor shape on cold plasma yeast inactivation - Ying Wang; Guanting Pan; Yining Li; Longtao Mu; Mingwei Zhao; Yu Zheng (Journal of Food Engineering, 2024)

The infrastructure cost of permafrost degradation for the Northern Hemisphere - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yuan Huang; Lei Guo; Jing Luo; Guoan Yin; Guohui Zhao; Cuicui Mu (Global Environmental Change, 2024)

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

Ultrahigh moisture resistance, highly sensitive and flame retardancy wearable strain sensor for agile water rescue, fire alarm and human motion detection - Qinghua Liu; Jiehui Li; Jinmei He; Leihuan Mu; Yuyu Xue; Yue Zhao; Hui Liu; Cai-Li Sun; Mengnan Qu (Chemical Engineering Journal, 2024)

Deciphering the intricate dielectric relaxation processes of cellulose paper: Extraction of distribution of relaxation time and analysis of degradation characteristics - Haoxiang Zhao; Jiangyang Zhan; Hao Yun; Haibao Mu; Daning Zhang; Lixuan An; Huanmin Yao; Guanjun Zhang (Carbohydrate Polymers, 2024)

Response of runoff-sediment processes to vegetation restoration patterns under different rainfall regimes on the Loess Plateau - Xiaoxue Guo; Min Du; Peng Gao; Peng Tian; Guangju Zhao; Xingmin Mu; Ren Geng (CATENA, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Significant enhancement of biomethane recovery in up-flow anaerobic sludge blanket reactor treating starch wastewater through oyster shells conditioning - Hui Mu; Qingyu Sun; Meng Zhong; Chunhui Zhao; Yongfang Zhang; Liguo Wang (Journal of Cleaner Production, 2023)

The gradient fabrication and optimization of metal-acid bifunctional catalysts for the hydrogenation of n-C16 to produce bio-jet fuel component - Junhao Sun; Yingying Yu; Chao Mu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Exposure to phthalates and their alternatives in relation to biomarkers of inflammation and oxidative stress in adults: evidence from NHANES 2017–2018 - Shihao Jin; Shanshan Cui; Xiaoyu Mu; Zhao Liu; Yu Han; Tingkai Cui; Wenjuan Xiong; Wei Xi; Xin Zhang (Environmental Science and Pollution Research, 2023)

The neurobehavioral impacts of typical antibiotics toward zebrafish larvae - Yining Zhang; Xue Li; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Guijie Hao; Xueping Ye; Shunlong Meng; Guohua Xiao; Jiandong Mu; Xiyan Mu; Jing Qiu; et al. (Chemosphere, 2023)

Bisphenol analogues induced social defects and neural impairment in zebrafish - Xiyan Mu; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Qi Jia; Chengju Wang; Tiejun Li; Yuanming Guo; Jing Qiu; Yongzhong Qian (Science of The Total Environment, 2023)

Historical and projected evolutions of glaciers in response to climate change in High Mountain Asia - Lin Yang; Guangju Zhao; Xingmin Mu; Yanli Liu; Peng Tian; Puqiong; Danzengbandian (Environmental Research, 2023)

Spatial and temporal variability in snow density across the Northern Hemisphere - Wenyu Zhao; Cuicui Mu; Li Han; Wen Sun; Yanhua Sun; Tingjun Zhang (CATENA, 2023)

Inoculum size-insensitive susceptibility determination of urine sample based on in-situ measurement of inducible enzyme activity after 20 min of antibiotic exposure - Wenshuai Wu; Yuanjie Suo; Qianbin Zhao; Gaozhe Cai; Yang Liu; Wei Jin; Ying Mu; Boran Zhang (Analytica Chimica Acta, 2023)

Systematic and dynamic impacts of the COVID-19 pandemic on marine economic development, air pollution and energy consumption: A case study of China's coastal regions - Chenggang Li; Yuanrui Zhang; Ziling Chen; Xue Wang; Mu Yue; Jiaqi Liu; Yuchun Jiang; Zhen Zhao; Guoli Cai (Ocean & Coastal Management, 2023)

Effects of different types of granular activated carbon on methanogenesis of carbohydrate-rich food waste: Performance, microbial communities and optimization - Hui Mu; Xiaofan Ding; Xiaoyu Zhu; Liguo Wang; Yongfang Zhang; Chunhui Zhao (Science of The Total Environment, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Enhanced hydrophobic microporous Pt/silica with high adsorption and catalytic oxidation for trace toluene removal - Mu Zhou; Shuangde Li; Mengjie Cao; Tao Wang; Linfeng Nie; Weiman Li; Feng Zhao; Yunfa Chen (Journal of Environmental Chemical Engineering, 2023)

Study on photodissociation and photoconversion characteristics of CS2 in O2/O3 environment using real-time conversion products obtained by UV-DOAS - Jie Gao; Mu Li; Huan Zhao; Yongqi Wu; Qiang Gao; Xijun Wu; Yucun Zhang; Yungang Zhang (Journal of Environmental Chemical Engineering, 2023)

Chaste honey in long term-storage: Occurrence and accumulation of Maillard reaction products, and safety assessment - Sha Yan; Min Zhang; Yuzhe Yuan; Guodong Mu; Haitao Xu; Tian Zhao; Yinchen Wang; Xiaofeng Xue (Food Chemistry, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

Preparation of porous hollow spherical MoOX/C catalyst for efficient extraction and oxidative desulfurization - Junzhen Guo; Baozhen Li; Danfeng Zhao; Liang Chu; Haibin Yang; Zhi Huang; Zhaohui Liu; Mu Yang; Ge Wang (Chemical Engineering Journal, 2023)

Biological neutralization of bauxite residue with fermented waste sludge and bio-acid, and the microbial ecological restoration - Dainan Qin; Xiaotong Tan; Xin Zhao; Lulu Qian; Yuanyuan Nie; Xiaolin Pan; Qun Gao; Mu Peng; Yang Liu; Xiaoyu Han (Chemical Engineering Journal, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Organic matter preservation conditions in the third member of the Shahejie Formation (Dongpu Depression, China) - Xiuyan Liu; Honghan Chen; Xiaoshui Mu; Hongan Zhang; Junjia Fan; Yahao Huang; Ke Zhao; Ahmed Mansour; Thomas Gentzis; Mehdi Ostadhassan (International Journal of Coal Geology, 2023)

Effects of florfenicol on the antioxidant and immune systems of Chinese soft-shelled turtle (Pelodiscus sinensis) - Yuqi Mu; Mengyan Lan; Yali Li; Zhao Zhang; Yueqiang Guan (Fish & Shellfish Immunology, 2023)

Hydro-mechanical behavior of unsaturated intact paleosol and intact loess - Qingyi Mu; Longlong Meng; Zhao Lu; Limin Zhang (Engineering Geology, 2023)

Electricity facilitates the lithium sorption from salt-lake brine by H3LiTi5O12 nanoparticles: Kinetics, selectivity and mechanism - Qiuyue Wang; Mu Li; Bing Zhao; Boyang Meng; Wutong Chen; Zekai Jiang; Xin He; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Lactate Improves Long-term Cognitive Impairment Induced By Repeated Neonatal Sevoflurane Exposures Through SIRT1-mediated Regulation of Adult Hippocampal Neurogenesis and Synaptic Plasticity in Male Mice - Li-Li Qiu; Xiao-Xiang Tan; Jiao-Jiao Yang; Mu-Huo Ji; Hui Zhang; Chunjie Zhao; Jiang-Yan Xia; Jie Sun (Molecular Neurobiology, 2023)

Rotifer distribution patterns in relation to dissolved organic matter in the middle reaches of Huai River Basin during the dry season - Leilei Luan; Liangmin Gao; Xudong Chen; Juan Ge; Ming Mu; Xiaoqing Chen; Xinglan Zhao; Zhen Zhang; Haiqiang Zhang (Environmental Science and Pollution Research, 2023)

Corrigendum to “Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity” [Toxicology 487 (2023) 1–13] - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Seismic behaviour of plate-reinforced composite coupling beams with RC slabs - Jianbo Tian; Yong Zhao; Penggang Tian; Wengeng Ren; Zhe Li; Lin Mu; Junlong Lu (Soil Dynamics and Earthquake Engineering, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Maximizing jet fuel production from n-hexadecane hydrocracking over Pt-supported Y catalysts: Importance of ideal hydrocracking characteristics - Yi Li; Chao Mu; Guangxin Chu; Yule Wang; Jing Xu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

Study on a galactose decomposition strain of Lactiplantibacillus plantarum MWLp-4 from human milk: Safety evaluating and key genes analysis of potential probiotic function - Xiaomei Zhang; Junhao Jin; Jinghong Zhao; Hui Nie; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2023)

Engineered metal coverage of anode catalyst layer enhancing cell reversal tolerance for proton exchange membrane fuel cells - Zheng Li; Haodong Huang; Yameng Wang; Yongbiao Mu; Yuting Jiang; Qing Zhang; Tianshou Zhao; Lin Zeng (Chemical Engineering Journal, 2023)

The dynamic amplification effect of a site with earth fissures: a case study in the Taiyuan Basin, China - Jiang Chang; Yahong Deng; Ge Cao; You Xuan; Nainan He; Xunchang Zhao; Huandong Mu (Journal of Seismology, 2023)

Quantifying climate and anthropogenic impacts on runoff using the SWAT model, a Budyko-based approach and empirical methods - Ruirui Xu; Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Wenyi Sun; Peng Gao (Hydrological Sciences Journal, 2023)

An artificial interfacial layer with biomimetic ionic channels towards highly stable Li metal anodes - Yiju Li; Tianshuai Wang; Junjie Chen; Xudong Peng; Minghui Chen; Bin Liu; Yongbiao Mu; Lin Zeng; Tianshou Zhao (Science Bulletin, 2023)

Evaluating the effectiveness of coastal environmental management policies in China: The case of Bohai Sea - Jinzhao Xiang; Tingwei Cui; Xuyan Li; Qian Zhang; Bing Mu; Rongjie Liu; Wenjing Zhao (Journal of Environmental Management, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Green recovery of Li, Ni, and Mn from spent xLi2MnO3·(1-x)LiMO2 cathode materials: Experimental study and mechanism analysis - Yifan Wang; Qijun Zhang; Xiaoxia Bai; Panpan Mu; Xiaoguang Zhang; Wei Wang; Zhe Tan; Zhenhuan Zhao; De'an Pan (Chemical Engineering Journal, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Microtremor-based analysis of the dynamic response characteristics of a site containing grouped earth fissures - Yahong Deng; You Xuan; Huandong Mu; Jiang Chang; Ge Cao; Nainan He; Xunchang Zhao; Longfei Sun (Earthquake Engineering and Engineering Vibration, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

In-situ anaerobic treatment removes the passivation layer of sponge iron to restore the nitrogen and phosphorus removal performance of SBR - Kaiyao Hu; Wenxuan Li; Hao Mu; Shuang Ren; Hongjuan Zhu; Kexin Zeng; Bo Wang; Jinming Liang; Qi Zhang; Lili Yang; Wei Zhao; Juqiang Xiao (Process Safety and Environmental Protection, 2023)

State constrained control strategy for unmanned surface vehicle trajectory tracking based on improved barrier Lyapunov function - Dongdong Mu; Lu Li; Guofeng Wang; Yunsheng Fan; Yongsheng Zhao; Xiaojie Sun (Ocean Engineering, 2023)

Optimum trim prediction for container ships based on machine learning - Haiwen Tu; Kai Xia; Enjin Zhao; Lin Mu; Jianglong Sun (Ocean Engineering, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Influence on physical properties and digestive characters of fermented coconut milk with different loading proportion of skimmed coconut drink using Lactiplantibacillus plantarum MWLp-4 from human milk mixing with commercial bacteria - Qing Zhao; Zining Wang; Zengxin Yu; Zhongyang Gao; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

A viologen-based conductive hydrogel enables iontophoresis devices powered by Mg biobattery - Yan Zhou; Shan Jiang; Xuenan Ma; Yueming Mu; Jiaxin Zhao; Qin Liang; Xiaoteng Jia; Danming Chao (Chemical Engineering Journal, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Response of soil erosion to vegetation restoration and terracing on the Loess Plateau - Peng Tian; Xiaojing Tian; Ren Geng; Guangju Zhao; Lin Yang; Xingmin Mu; Peng Gao; Wenyi Sun; Yulin Liu (CATENA, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Sequence-paleogeography and coal accumulation of the Late Carboniferous – Early Permian paralic successions in western Shandong Province, northern China - Yanwen Shao; Fenghua Zhao; Guangyuan Mu; Bin Sun; Kaihua Liang; Dongdong Wang; Jing Lu; Shimin Ma; Longyi Shao (Marine and Petroleum Geology, 2023)

Sediment source tracing during flood events in the Huangfu River basin in the northern Loess Plateau, China - Xiaojing Tian; Peng Tian; Guangju Zhao; José A. Gómez; Jianying Guo; Xingmin Mu; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Nicotine exposure exacerbates silica-induced pulmonary fibrosis via STAT3-BDNF-TrkB-mediated epithelial-mesenchymal transition in alveolar type II cells - Haoming Chen; Xinrong Tao; Hangbing Cao; Bing Li; Qixian Sun; Wenyang Wang; Yuanjie Zou; Min Mu; Huihui Tao; Yehong Zhao; Deyong Ge (Food and Chemical Toxicology, 2023)

Internal force redistribution caused by cracking of concrete in composite frame structures under lateral load - Mu-Xuan Tao; Yu-Lun Wang; Ji-Zhi Zhao (Engineering Structures, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

Light Intensity and Photoperiod Interaction Affects the Survival, Development, Molting and Apoptosis-Related Genes of Swimming Crab Portunus trituberculatus Larvae - Yun Zhao; Juan Dou; Hanying Xu; Zhen Ma; Yangfang Ye; Changkao Mu; Weiwei Song; Zhiming Ren; Chunlin Wang; Ce Shi (Fishes, 2023)
A 19-day experiment was conducted to investigate the optimal light intensity and photoperiod combination for larval swimming crabs Portunus trituberculatus in terms of survival, development, and apoptosis-related gene expression. Two photoperiods, i.e., 12 and 18 h photophases, and three light intensities, i.e., 126.08, 173.17, and 191.53 μmol m−2 s−1, were used in the study. The results showed that the cumulative survival rate (CSR) of larvae decreased with the increasing light intensity, and the adverse effect of high light intensity was only observed in long photophase groups. On the contrary, a long photophase and low light intensity elevated the CSR from zoea III to juvenile crabs. A long photophase also accelerated the development of zoea III larvae and upregulated the molting-related (ecr and rxr) and apoptosis-related (jnk, p53, and bcl-2) gene expressions. Taken together, the present study suggested that the light intensity and the photoperiod had a combined effect on P. trituberculatus larvae. The optimal light intensity and photoperiod for P. trituberculatus larvae were 126.08 μmol m−2 s−1 and an 18 h photophase, respectively.

Experimental study on in-plane behavior of composite frame slabs and the influence of out-of-plane effect - Wen-Hao Pan; Mu-Xuan Tao; Chuan-Hao Zhao; Ran Ding; Li-Yan Xu (Engineering Structures, 2023)

Cation mixing effect regulation by niobium for high voltage single-crystalline nickel-rich cathodes - Zhikun Zhao; Chunli Li; Ziyue Wen; Zhuolin Yang; Shijie Lu; Xinyu Zhang; Shi Chen; Borong Wu; Feng Wu; Daobin Mu (Chemical Engineering Journal, 2023)

An efficient green-emitting quantum dot with near-unity quantum yield and suppressed Auger recombination for high-performance light-emitting diodes - Xiaokun Fan; Zhen Mu; Zhao Chen; Yunfeng Zhan; Fanyuan Meng; Yang Li; Guichuan Xing; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

Gully erosion and expansion mechanisms in loess tablelands and the scientific basis of gully consolidation and tableland protection - Zhao Jin; Jianbing Peng; Jianqi Zhuang; Li Feng; Aidi Huo; Xingmin Mu; Wenlong Wang (Science China Earth Sciences, 2023)

A novel nanoparticle surface-constrained CRISPR-Cas12a 3D DNA walker-like nanomachines for sensitive and stable miRNAs detection - Xin Wang; Xiaomei Mu; Jinshen Li; Guang Liu; Shulin Zhao; Jianniao Tian (Analytica Chimica Acta, 2023)

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

Performance and changes of high‐resolution (1 km) surface air temperature in Northern Hemisphere permafrost regions - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yaohua Zhao; Xuanjia Li; Weiwei Tian; Cong Chen; Benben Liang; Xiaodong Li; Cuicui Mu (International Journal of Climatology, 2023)
Surface air temperatures are significant indicators of environmental and climatic change that affect a diverse set of physical systems including permafrost. Most temperature products, such as gridded or reanalysis data, are still at a relatively low spatial resolution, limiting the ability to simulate heterogeneous permafrost changes and leading to large uncertainties. Here we apply a downscaling method based on elevation to obtain high‐resolution surface air temperatures from the sixth Coupled Model Intercomparison Project in Northern Hemisphere permafrost regions. Root‐mean‐square errors and mean absolute errors after downscaling are reduced by 34 and 37%, respectively, relative to meteorological site data and gridded observations from the Climatic Research Unit. Compared to the downscaled surface air temperature data, nondownscaled model projections overestimate by 0.12–0.39°C in the discontinuous, isolated, and sporadic permafrost regions and underestimate up to 0.18°C in the continuous permafrost region under different emission scenarios. The warming rates in Northern Hemisphere permafrost regions were 0.093°C/10 year during the historical (1850–2014) period and are projected to be 0.22°C/10 year for SSP1‐2.6, 0.48°C/10 year for SSP2‐4.5, 0.75°C/10 year for SSP3‐7.0, and 0.95°C/10 year for SSP5‐8.5 during 2015–2100, which is 1.4–1.6 times the warming of nonpermafrost regions. Warming rates in high latitudes are 1.2–1.7 times higher than those in high‐elevation regions. Continuous permafrost regions' warming will be 1.2–1.4 times higher than in other permafrost regions. For permafrost with high ground ice content, warming will be 1.1 times greater than in permafrost regions with medium or low ground ice content.

Artificial intelligence-aided preparation of perovskite SrFexZr1-xO3-δ catalysts for ozonation degradation of organic pollutant concentrated water after membrane treatment - Xu Wang; Yanan Zhang; Cheng Zhang; Huangzhao Wei; Haibo Jin; Zhao Mu; Xiaofei Chen; Xinru Chen; Ping Wang; Xiaoyan Guo; Fuchen Ding; Xiaowei Liu; et al. (Chemosphere, 2023)

Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Atmospheric dustfall exhibits consistent sedimentary sorting with height evidenced by grain size characteristics - Yongchong Lin; Guijin Mu; Xue Zhao; Lishuai Xu; Jifeng Zhang (Science of The Total Environment, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Effects of Pediococcus acidilactici and Rhizopus Oryzae on microbiota and metabolomic profiling in fermented dry-cure mutton sausages - Li Jiang; Yingchun Mu; Wei Su; Haiyong Tian; Mouming Zhao; Guowan Su; Chi Zhao (Food Chemistry, 2023)

Bifunctional electrocatalyst junction engineering: CoP nanoparticles in-situ anchored on Co3(Si2O5)2(OH)2 nanosheets for highly efficient water splitting - Yang Mu; Yifu Zhang; Ziyi Feng; Xueying Dong; Xuyang Jing; Xiaoyu Pei; Yunfeng Zhao; Zongkui Kou; Changgong Meng (Chemical Engineering Journal, 2023)

Magnesium Hydroxide Slurry Coagulation-Adsorption Performance for Reactive Orange Removal Assisted with PAM - Xiaoli Deng; Jianhai Zhao; Xiuming Qiu; Yingying Duan; Xiaoyu Ren; Wenpu Li; Rong Mu; Hongying Yuan (Water, Air, & Soil Pollution, 2023)

Flavobacterium potami sp. nov., a multi-metal resistance genes harbouring bacterium isolated from shallow river silt - Shucheng Li; Sidi Mao; Weidong Mu; Bai Guo; Chen Li; Qing Zhu; Xiaoxiao Hou; Yanfang Zhao; Shuzhen Wei; Hongliang Liu; Aiju Liu (Antonie van Leeuwenhoek, 2023)

Effects of dietary supplementation with astragalus (Astragalus membranaceus) root or leaf meal on the hematology, serum biochemical parameters, histomorphology, oxidative status, and resistance of Phoxinus lagowskii against bacterial infection - Tiehui Yao; Tianxu Zhang; Qihan Zhao; Sihan Wang; Yingqiao Chen; Zhaoyang Ning; Mingyang Sun; Haishui Zhou; Weijie Mu (Aquaculture, 2023)

Atmospheric ammonia in the rural North China Plain during wintertime: Variations, sources, and implications for HONO heterogeneous formation - Pengfei Liu; Hui Chen; Yifei Song; Chaoyang Xue; Can Ye; Xiaoxi Zhao; Chenglong Zhang; Junfeng Liu; Yujing Mu (Science of The Total Environment, 2023)

Two-year online measurements of volatile organic compounds (VOCs) at four sites in a Chinese city: Significant impact of petrochemical industry - Jiangshan Mu; Yingnan Zhang; Zhiyong Xia; Guolan Fan; Min Zhao; Xiaoyan Sun; Yuhong Liu; Tianshu Chen; Hengqing Shen; Zhanchao Zhang; Huaicheng Zhang; Guang Pan; et al. (Science of The Total Environment, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Effect of 4 °C and ice temperature on umami-enhancing nucleotides of conditioned pork - Yin Zhang; Yingjie Zhang; Hui Li; Ting Bai; Qin Qian; Haichuan Peng; Yunlong Mu; Linguo Wang; Baohua Liu; Jie Chen; Zhongli Pan; Dayu Liu; et al. (Food Chemistry, 2023)

Effects of vegetation restoration on soil infiltrability and preferential flow in hilly gully areas of the Loess Plateau, China - Dexun Qiu; Ruirui Xu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (CATENA, 2023)

The Prevention Effect of Bacillus subtilis on Escherichia coli–Induced Mastitis in Mice by Suppressing the NF-κB and MAPK Signaling Pathways - Xiaoyu Hu; Ruibo Tang; Caijun Zhao; Ruiying Mu; Ying Wang; Yongguo Cao; Naisheng Zhang; Yunhe Fu (Probiotics and Antimicrobial Proteins, 2023)

dmrt3, nom1, abce1, and pkmyt1 play key roles in gonadal sex determination in Acrossocheilus fasciatus - Yuting Ren; Yi Mu; Bo Zhao; Yang Gao; Xiaoxin Dai; Zhangjie Chu (Aquaculture International, 2023)

Spatial scale‐dependent dilution effects of biodiversity on plant diseases in grasslands - Xiang Liu; Yao Xiao; Ziyuan Lin; Xingxing Wang; Kui Hu; Mu Liu; Yimin Zhao; Yanwen Qi; Shurong Zhou (Ecology, 2023)
The rapid biodiversity losses of the Anthropocene have motivated ecologists to understand how biodiversity affects infectious diseases. Spatial scale is thought to moderate negative biodiversity–disease relationships (i.e., dilution effects) in zoonotic diseases, whereas evidence from plant communities for an effect of scale remains limited, especially at local scales where the mechanisms (e.g., encounter reduction) underlying dilution effects actually work. Here, we tested how spatial scale affects the direction and magnitude of biodiversity–disease relationships. We utilized a 10‐year‐old nitrogen addition experiment in a Tibetan alpine meadow, with 0, 5, 10, and 15 g/m 2 nitrogen addition treatments. Within the treatment plots, we arranged a total of 216 quadrats (of either 0.125 × 0.125 m, 0.25 × 0.25 m or 0.5 × 0.5 m size) to test how the sample area affects the relationship between plant species richness and foliar fungal disease severity. We found that the dilution effects were stronger in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, compared with 0.5 × 0.5 m quadrats. There was a significant interaction between species richness and nitrogen addition in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, indicating that a dilution effect was more easily observed under higher levels of nitrogen addition. Based on multigroup structural equation models, we found that even accounting for the direct impact of nitrogen addition (i.e., “nitrogen‐disease hypothesis”), the dilution effect still worked at the 0.125 × 0.125 m scale. Overall, these findings suggest that spatial scale directly determines the occurrence of dilution effects, and can partly explain the observed variation in biodiversity–disease relationships in grasslands. Next‐generation frameworks for predicting infectious diseases under rapid biodiversity loss scenarios need to incorporate spatial information.

Ship Dynamic Positioning Output Feedback Control with Position Constraint Considering Thruster System Dynamics - Dongdong Mu; Yupei Feng; Guofeng Wang; Yunsheng Fan; Yongsheng Zhao; Xiaojie Sun (Journal of Marine Science and Engineering, 2023)
In order to simultaneously address the issues of ship operating area limitation, unknown time-varying disturbances, immeasurable ship speed, unknown dynamics, and input saturation, this paper investigates the position-constrained ship dynamic positioning output feedback control, taking thruster system dynamics into account. Firstly, a barrier Lyapunov function (BLF) is utilized to limit the ship position inside the dynamic positioning system’s acceptable working range and to limit the ship position error. Second, the set total disturbance, which is made up of unknown time-varying disturbances and unknown dynamics and is further handled by the control strategy, is estimated using a fixed-time extended state observer (FDESO). Additionally, the thruster system dynamics equations are incorporated into the controller design process so that the generated thrust signal varies gradually without abrupt fluctuations, in keeping with engineering realities. Furthermore, the thruster input saturation issue is dealt with using a finite-time auxiliary dynamic system. Finally, a robust control term is introduced to handle the errors generated in the controller design. The stability proof section demonstrates that the designed control strategy can cause the ship to arrive and maintain at the desired location and heading, as well as stay continuously inside the designated operating area with all signals of the closed-loop control system being consistently and eventually bounded. The simulation results demonstrate that the proposed system is valid.

Xenobiotic-sensing nuclear receptors as targets for phthalates-induced lung injury and antagonism of lycopene - Yu-Sheng Shi; Yi Zhao; Xue-Nan Li; Mu-Zi Li; Jin-Long Li (Chemosphere, 2023)

Formation mechanisms and atmospheric implications of summertime nitrous acid (HONO) during clean, ozone pollution and double high-level PM2.5 and O3 pollution periods in Beijing - Huiying Xuan; Yaqi Zhao; Qingxin Ma; Tianzeng Chen; Jun Liu; Yonghong Wang; Chang Liu; Yafei Wang; Yongchun Liu; Yujing Mu; Hong He (Science of The Total Environment, 2023)

Spatial distribution characteristics and prediction of fluorine concentration in groundwater based on driving factors analysis - Mu-Yuan Lu; Yuan Liu; Gui-Jian Liu; Yong-Li Li; Jin-Zhao Xu; Guan-Yu Wang (Science of The Total Environment, 2023)

Characterizing the spatiotemporal distribution of dissolved organic matter (DOM) in the Yongding River Basin: Insights from flow regulation - Yijuan Bai; Shurong Zhang; Enlin Mu; Yinjun Zhao; Lirong Cheng; Yi Zhu; Yumin Yuan; Yingying Wang; Aizhong Ding (Journal of Environmental Management, 2023)

Effects of Jiuqu inoculating Rhizopus oryzae Q303 and Saccharomyces cerevisiae on chemical components and microbiota during black glutinous rice wine fermentation - Chi Zhao; Wei Su; Yingchun Mu; Lixin Luo; Mouming Zhao; Shuyi Qiu; Guowan Su; Li Jiang (International Journal of Food Microbiology, 2023)

Physicochemical characteristics and biological activities of grape polysaccharides collected from different cultivars - Xiangpeng Leng; Wenjun Miao; Jizhen Li; Yuanxia Liu; wenwen Zhao; Qian Mu; Qiu Li (Food Research International, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Construction of novel Heat-conducting Cu-based MOF nanocomposite (HK-mBNNS/PVDF) film for highly efficient Ad-/desorption of toluene - Junjie Li; Liming Liu; Syed Jalil Shah; Ying Tang; Shanliang Jiang; Guangyuan Mu; Quanru Man; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2023)

Filling the gap between molecular and aggregate states: how does molecular packing affect photophysical properties? - Xu-Min Cai; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Tianqi Mu; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Linkages between soil erosion and long-term changes of landscape pattern in a small watershed on the Chinese Loess Plateau - Chaoliang Chen; Guangju Zhao; Yatong Zhang; Yunpeng Bai; Peng Tian; Xingmin Mu; Xiaojing Tian (CATENA, 2023)

Effects of sponge iron dosage on nitrogen removal performance and microbial community structure in sequencing batch reactors - Hongjuan Zhu; Wenxuan Li; Xinjuan Chen; Hao Mu; Kaiyao Hu; Shuang Ren; Yuzhuo Peng; Ruifeng Zhao; Yae Wang (Bioresource Technology, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Genomewide identification and analysis of the OSCA gene family in barley (Hordeum vulgare L.) - Qian Cai; Yuexue Wang; Shoufei Ni; Jingjiao Mu; Mengdi Liu; Yanfang Wang; Yanhong Zhao (Journal of Genetics, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Precise orbit determination for the Haiyang-2D satellite using new onboard BDS-3 B1C/B2a signal measurements - Min Li; Renhai Mu; Kecai Jiang; Youcun Wang; Xuanxuan Zhang; Chuntao Chang; Qile Zhao (GPS Solutions, 2022)

The utilization of physically based models and GIS techniques for comprehensive risk assessment of storm surge: A case study of Huizhou - Si Wang; Lin Mu; Hao Qin; Lizhe Wang; Zhenfeng Yao; Enjin Zhao (Frontiers in Marine Science, 2022)
Quantitative analyses of storm surge risk, which are mostly focused on physical vulnerability, have been widely used to help coastal communities mitigate impacts and damage. Such assessments, however, overlook the social aspect of vulnerability in storm surge risk. By considering both the community’s social vulnerability and buildings’ physical vulnerability, this study proposed a methodology that incorporates social vulnerability into the framework for making quantitative risk assessments of storm surge using a coupled hydrodynamic and wave model, Geographical Information System (GIS) techniques, and the Principal Component Analysis (PCA) method. The coastal area of Huizhou was chosen as the case study due to its high concentration of oil and gas infrastructure in China’s southern Guangdong Province. By combining hazard, exposure, physical vulnerability, and social vulnerability, it was possible to explore the effect of social vulnerability on the physical vulnerability-based risk assessment of storm surge and determine the overall risk level. First, the Gumbel distribution was utilized to establish five representative and plausible hypothetical typhoon events with different return periods (10, 20, 50, 100, and 1000 years) for the study area. Then, using the well-validated fully-coupled model, the Simulating Waves Nearshore (SWAN) model and the ADvanced CIRCulation (ADCIRC) model, storm surge simulations for defined return periods were run, and the geographical distribution of the maximum surge elevations displayed on a GIS platform was used to assess hazard levels. In terms of the physical aspect, the depth-damage functions for buildings were established to estimate direct economic losses and assign risk levels accordingly. For the social vulnerability of a community, a composite score was computed using the PCA method by combining and aggregating indicators representing various characteristics of the social group. The results show that the overall risk level, taking into account both social vulnerability and physical vulnerability, has decreased on average. It suggests that social vulnerability-based risk assessment may account for a significant portion of the overall risk assessment, which is frequently overlooked in traditional storm surge risk assessment. Additionally, the comprehensive and precise risk maps can assist local policymakers in identifying areas at different risk levels and developing evacuation plans, thereby minimizing potential losses, especially in high-risk areas.

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Changes in extreme precipitation in the Wei River Basin of China during 1957–2019 and potential driving factors - Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (Theoretical and Applied Climatology, 2022)

Physiological and Molecular Analyses of Low-Salinity Stress Response in the Cuttlefish (Sepia pharaonis) Juveniles - Hongwei Xin; Kunlan Wu; Yimeng Yuan; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Several major issues concerning the environmental transmission and risk prevention of SARS-CoV-2 - Jin Ma; Jian Xu; Xiaoli Zhao; Shouliang Huo; Xiaoli Duan; Yunsong Mu; Ying Wang; Yuan Wei; Jiang Chang; Xiaowei Jin; Fengchang Wu (Science China Earth Sciences, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Xiaoxin Dai; Lijun Qiu; Han Zhang; Chunying Xu; Bo Zhao; Yang Gao; Haidong Li; Yi Mu; Zhangjie Chu (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Identification of a candidate gene underlying qHKW3, a QTL for hundred-kernel weight in maize - Qin Sun; Aoqing Hu; Luyao Mu; Hailiang Zhao; Yao Qin; Dianming Gong; Fazhan Qiu (Theoretical and Applied Genetics, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Spatial-temporal Analysis and Prediction of Precipitation Extremes: A Case Study in the Weihe River Basin, China - Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (Chinese Geographical Science, 2022)

Preparation and Evaluation of Novel Supersaturated Solid Dispersion of Magnolol - Jing Zhao; Pan Gao; Chengqiao Mu; Jingqi Ning; Wenbin Deng; Dongxu Ji; Haowei Sun; Xiangrong Zhang; Xinggang Yang (AAPS PharmSciTech, 2022)

Variations of pan evaporation and its attribution from 1961 to 2015 on the Loess Plateau, China - Jinfei Hu; Guangju Zhao; Pengfei Li; Xingmin Mu (Natural Hazards, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Standard- vs. low-dose rivaroxaban in patients with atrial fibrillation: a systematic review and meta-analysis - Guangyan Mu; Hanxu Zhang; Zhiyan Liu; Qiufen Xie; Shuang Zhou; Zining Wang; Zhe Wang; Kun Hu; Jingyi Hou; Nan Zhao; Qian Xiang; Yimin Cui (European Journal of Clinical Pharmacology, 2022)

Identification of WRKY transcription factors responding to abiotic stresses in Brassica napus L. - Hao Chen; Yongfeng Wang; Jiong Liu; Tian Zhao; Cuiling Yang; Qunying Ding; Yanfeng Zhang; Jianxin Mu; DaoJie Wang (Planta, 2022)

Hydrogeochemistry, identification of hydrogeochemical evolution mechanisms, and assessment of groundwater quality in the southwestern Ordos Basin, China - Xiao Zhang; Rong Zhao; Xiong Wu; Wenping Mu (Environmental Science and Pollution Research, 2022)

Water-inrush Risk through Fault Zones with Multiple Karst Aquifers Underlying the Coal Floor: A Case Study in the Liuzhuang Coal Mine, Southern China - Jian Zhang; Liangliang Guo; Wenping Mu; Shouqiang Liu; Dexing Zhao (Mine Water and the Environment, 2021)

Physical and Numerical Investigations on Wave Run-Up and Dissipation under Breakwater with Fence Revetment - Enjin Zhao; Lin Mu; Zhaoyang Hu; Xinqiang Wang; Junkai Sun; Zhiyong Zhang (Journal of Marine Science and Engineering, 2021)
Revetment elements and protective facilities on a breakwater can effectively weaken the impact of waves. In order to resist storm surges, there is a plan to build a breakwater on the northern shore of Meizhou Bay in Putian City, China. To better design it, considering different environmental conditions, physical and numerical experiments were carried out to accurately study the effects of the breakwater and its auxiliary structures on wave propagation. In the experiments, the influence of the wave type, initial water depth, and the structure of the fence plate are considered. The wave run-up and dissipation, the wave overtopping volume, and the structure stability are analyzed. The results indicate that the breakwater can effectively resist the wave impact, reduce the wave run-up and overtopping, and protect the rear buildings. In addition, under the same still water depth and significant wave height, the amount of overtopped water under regular waves is larger than that under irregular waves. With the increase of the still water depth and significant wave height, the overtopped water increases, which means that when the storm surge occurs, damage on the breakwater under the high tide level is greater than that under the low tide level. Besides, the fence plate can effectively dissipate energy and reduce the overtopping volume by generating eddy current in the cavity. Considering the stability and the energy dissipation capacity of the fence plate, it is suggested that a gap ratio of 50% is reasonable.

Grain size characteristics of the sand silt layers in the ancient delta of the dried Lop Nur lake (east Tarim Basin) and their environmental implications - Yongchong Lin; Guijin Mu; Lishuai Xu; Xue Zhao (Arabian Journal of Geosciences, 2021)

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

Developing the non‐dimensional framework for water distribution formulation to evaluate sprinkler irrigation* - Ang Li; Xinyuan Mu; Xia Zhao; Jiamin Xu; Majid Khayatnezhad; Reza Lalehzari (Irrigation and Drainage, 2021)
Improving the application efficiency and leaching of solutes from the root zone in a sprinkler irrigation system are directly related to the uniformity of water distribution at the field surface. The coefficient of uniformity and distribution uniformity are affected by changes in wind speed and its direction, sprinkler characteristics and variations in operating pressure. The objective of this paper is to present modified equations for evaluating pressurized irrigation systems based on non‐dimensional infiltrated depths. The equations were obtained by four data groups including the average of the measured infiltration depths in any quarter. Coefficient of uniformity (CU), distribution uniformity (DU), application efficiency ( E a ) and deep percolation (DP) were used as performance indicators to evaluate the sprinkler irrigation system. The suggested method was compared to the existing approach to assess the evaluation indicators. Three data sets of observed information for wheel‐move, permanent solid set and semi‐solid set irrigation systems were collected in Chaharmahal and Bakhtiari provinces to evaluate the proposed formulation. Furthermore, the relationships between CU and DU were analysed for three scenarios of infiltration depth. Results show that the application efficiency was 12% less than previous equations because of using four average values.

Cytotoxic, clonal fidelity, and antioxidant evaluation of in vitro propagated Vitex negundo var. cannabifolia - Xue Meng; Fangfang Mu; Zeyu Zhang; Xinru Wu; Tiantian Gao; Fenglan Zhao; Jianping Xue; Yongbo Duan; Haijun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Contributions of climate change and human activities to runoff and sediment discharge reductions in the Jialing River, a main tributary of the upper Yangtze River, China - Yiting Shao; Yi He; Xingmin Mu; Guangju Zhao; Peng Gao; Wenyi Sun (Theoretical and Applied Climatology, 2021)

A review of the ecohydrology discipline: Progress, challenges, and future directions in China - Jun Xia; Yongyong Zhang; Xingmin Mu; Qiting Zuo; Yujian Zhou; Guangju Zhao (Journal of Geographical Sciences, 2021)

Transmission of SARS-CoV-2 virus and ambient temperature: a critical review - Yunsong Mu; Meichen Shao; Buqing Zhong; Yiqun Zhao; Kenneth M. Y. Leung; John P. Giesy; Jin Ma; Fengchang Wu; Fangang Zeng (Environmental Science and Pollution Research, 2021)

Runx2 deficiency in junctional epithelium of mouse molars decreases the expressions of E-cadherin and junctional adhesion molecule 1 - Yuan Tian; Haiyu Mu; Aiqin Wang; Yan Gao; Zhiheng Dong; Yang Zhao; Cong Li; Li Zhang; Yuguang Gao (Journal of Molecular Histology, 2021)

Response of winter-wheat grain yield and water-use efficiency to irrigation with activated water on Guanzhong Plain in China - Guoqing Zhao; Yan Mu; Yanhui Wang; Li Wang (Irrigation Science, 2021)

Serum Ceruloplasmin Is the Candidate Predictive Biomarker for Acute Aortic Dissection and Is Related to Thrombosed False Lumen: a Propensity Score–Matched Observational Case–Control Study - Changcheng Ma; Haibin Zhao; Feng Shi; Mu Li; Xun Liu; Chao Ji; Yanshuo Han (Biological Trace Element Research, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

High Spatial Resolution and High Temporal Frequency (30-m/15-day) Fractional Vegetation Cover Estimation over China Using Multiple Remote Sensing Datasets: Method Development and Validation - Xihan Mu; Tian Zhao; Gaiyan Ruan; Jinling Song; Jindi Wang; Guangjian Yan; Tim R. Mcvicar; Kai Yan; Zhan Gao; Yaokai Liu; Yuanyuan Wang (Journal of Meteorological Research, 2021)

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

A high-resolution melting analysis method for the effective discrimination of three Sepia species - Yun Zhao; Weiwei Song; Ronghua Li; Chunlin Wang; Changkao Mu (Journal of Consumer Protection and Food Safety, 2020)

Meteorological drought risk in the Daqing River Basin, North China: current observations and future projections - Wenbin Mu; Fuliang Yu; Yuping Han; Weixi Ma; Yong Zhao (Stochastic Environmental Research and Risk Assessment, 2020)

Dissection and validation of a QTL cluster linked to Rht-B1 locus controlling grain weight in common wheat (Triticum aestivum L.) using near-isogenic lines - Panfeng Guan; Xueyi Shen; Qing Mu; Yongfa Wang; Xiaobo Wang; Yongming Chen; Yue Zhao; Xiyong Chen; Aiju Zhao; Weiwei Mao; Yiwen Guo; Mingming Xin; et al. (Theoretical and Applied Genetics, 2020)

Dual-Emitting N/S-Doped Carbon Dots-Based Ratiometric Fluorescent and Light Scattering Sensor for High Precision Detection of Fe(III) Ions - Zhiyan Chen; Xueqin Xu; Dongling Meng; Honglin Jiang; Yun Zhou; Shouai Feng; Zhao Mu; Yaling Yang (Journal of Fluorescence, 2020)

Analysis of melting reconstruction treatment and cement solidification on ultra-risk municipal solid waste incinerator fly ash–blast furnace slag mixtures - Zhongtao Luo; Liugang Chen; Meixiang Zhang; Lei Liu; Jun Zhao; Yuandong Mu (Environmental Science and Pollution Research, 2020)

Hyperprogressive disease in patients with advanced renal cell carcinoma: a new pattern of post-treatment cancer behavior - Zhong Zheng; Ke Wu; Zhixian Yao; Xingyu Mu; Hantao Wu; Weiguang Zhao; Leilei Cheng; Zhihong Liu (Immunologic Research, 2020)

Neuroprotective effects of miR-532-5p against ischemic stroke - Jingwei Mu; Xi Cheng; Shanshan Zhong; Xiaohong Chen; Chuansheng Zhao (Metabolic Brain Disease, 2020)

Comparison of metabolites in juice, seed and peel of sea buckthorn (Hippophae rhamnoides L. subsp. sinensis) - Chuangyun Wang; Menglin Lei; Hong Zhang; Lijuan Zhao; Zhixin Mu; Meixia Wang; Jianhua Zhang; Yan Deng; Li Zhao (Journal of Plant Biochemistry and Biotechnology, 2020)

The Activation of Heat-Shock Protein After Copper(II) and/or Arsenic(III)-Induced Imbalance of Homeostasis, Inflammatory Response in Chicken Rectum - Xin Yang; Hongjing Zhao; Yu Wang; Juanjuan Liu; Menghao Guo; Dongxue Fei; Mengyao Mu; Mingwei Xing (Biological Trace Element Research, 2020)

Noncoding RNAs: functional regulatory factors in tomato fruit ripening - Lili Ma; Jianlou Mu; Donald Grierson; Yunxiang Wang; Lipu Gao; Xiaoyan Zhao; Benzhong Zhu; Yunbo Luo; Kai Shi; Qing Wang; Jinhua Zuo (Theoretical and Applied Genetics, 2020)

Molecular characterization of a novel fusarivirus infecting the plant-pathogenic fungus Botryosphaeria dothidea - Wenyi Liu; Du Hai; Fan Mu; Xiaojing Yu; Yingtong Zhao; Bangling He; Jiatao Xie; Daohong Jiang; Huixiang Liu (Archives of Virology, 2020)

A time-resolved dual transcriptome analysis reveals the molecular regulating network underlying the compatible/incompatible interactions between cabbage (Brassica oleracea) and Fusarium oxysporum f. sp. conglutinans - Xing Liu; Cunbao Zhao; Limei Yang; Mu Zhuang; Yangyong Zhang; Yong Wang; Zhiyuan Fang; Honghao Lv (Plant and Soil, 2020)

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)

Distinguishing the effects of vegetation restoration on runoff and sediment generation on simulated rainfall on the hillslopes of the loess plateau of China - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Xuejin Tan (Plant and Soil, 2020)

Hydrogen-induced tolerance against osmotic stress in alfalfa seedlings involves ABA signaling - Kiprotich Felix; Jiuchang Su; Rongfei Lu; Gan Zhao; Weiti Cui; Ren Wang; Hualun Mu; Jin Cui; Wenbiao Shen (Plant and Soil, 2019)

Elemental imbalance elicited by arsenic and copper exposures leads to oxidative stress and immunotoxicity in chicken gizzard, activating the protective effects of heat shock proteins - Menghao Guo; Hongjing Zhao; Yu Wang; Juanjuan Liu; Dongxue Fei; Xin Yang; Mengyao Mu; Mingwei Xing (Environmental Science and Pollution Research, 2019)

Quantifying the impacts of human activities on runoff and sediment load changes in a Loess Plateau catchment, China - Jinfei Hu; Guangju Zhao; Xingmin Mu; Peng Tian; Peng Gao; Wenyi Sun (Journal of Soils and Sediments, 2019)

MicroRNA transcriptome analysis of poly I:C-stimulated and PRRSV-infected porcine alveolar macrophages - Junjing Wu; Ziyun Ji; Mu Qiao; Xianwen Peng; Huayu Wu; Zhongxu Song; Haizhong Zhao; Guisheng Liu; Fenge Li; Shuqi Mei (Journal of Applied Genetics, 2019)

A GNSS/INS-integrated system for an arbitrarily mounted land vehicle navigation device - Mengxue Mu; Long Zhao (GPS Solutions, 2019)

A Novel Application of Fluorine Doped Carbon Dots Combining Vortex-Assisted Liquid-Liquid Microextraction for Determination of 4-Nitrophenol with Spectrofluorimetric Method - Shouai Feng; Zhao Mu; Hong Liu; Jiangfeng Huang; Xiaolan Li; Yaling Yang (Journal of Fluorescence, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Rice-paddy field acts as a buffer system to decrease the terrestrial characteristics of dissolved organic matter exported from a typical small agricultural watershed in the Three Gorges Reservoir Area, China - Jiang Liu; Tao Jiang; Dolly N. Kothawala; Qilei Wang; Zheng Zhao; Dingyong Wang; Zhijian Mu; Jinzhong Zhang (Environmental Science and Pollution Research, 2019)

Channel Sandstone Architecture Characterization by Seismic Simulation - Hongwei Liang; Xiaoqing Zhao; Longxin Mu; Zifei Fan; Lun Zhao; Shenghe Wu (Journal of Earth Science, 2019)

Sea Level Prediction in the Yellow Sea From Satellite Altimetry With a Combined Least Squares-Neural Network Approach - Jian Zhao; Yanguo Fan; Yuxiang Mu (Marine Geodesy, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Rainfall erosivity and sediment load over the Poyang Lake Basin under variable climate and human activities since the 1960s - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Qiang Yu (Theoretical and Applied Climatology, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Tripartite interactions between jasmonic/salicylic acid pathways, western flower thrips, and thrips-transmitted tomato zonate spot virus infection in Capsicuum annuum - Xue Zheng; Yong Chen; Lihua Zhao; Yongdui Chen; Limin Zheng; Kuanyu Zheng; Ye Mu; Xingyue Zhao; Yulin Gao; Jie Zhang (Arthropod-Plant Interactions, 2019)

Influence of vegetation restoration on soil physical properties in the Loess Plateau, China - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; John Tatarko; Xuejin Tan (Journal of Soils and Sediments, 2019)

Source discrimination of mine water inrush using multiple methods: a case study from the Beiyangzhuang Mine, Northern China - Qiang Wu; Wenping Mu; Yuan Xing; Cheng Qian; Jianjun Shen; Yang Wang; Dekang Zhao (Bulletin of Engineering Geology and the Environment, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

Streptomyces lutosisoli sp. nov., a novel actinomycete isolated from muddy soil - Yue Shen; Tianyu Sun; Shanwen Jiang; Shan Mu; Dongmei Li; Xiaowei Guo; Jianli Zhang; Junwei Zhao; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Nonomuraea rhizosphaerae sp. nov., an actinomycete isolated from the rhizosphere soil of a rubber tree (Hevea brasiliensis Muell. Arg) - Junwei Zhao; Shan Mu; Qiannan Zhao; Shanwen Jiang; Peng Cao; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Variations in extreme precipitation on the Loess Plateau using a high-resolution dataset and their linkages with atmospheric circulation indices - Guangju Zhao; Jianqing Zhai; Peng Tian; Limei Zhang; Xingmin Mu; Zhengfeng An; Mengwei Han (Theoretical and Applied Climatology, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

The levels of polycyclic aromatic hydrocarbons (PAHs) in human milk and exposure risk to breastfed infants in petrochemical industrialized Lanzhou Valley, Northwest China - Li Wang; Aiping Liu; Yuan Zhao; Xi Mu; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2018)

RNAi-mediated SLC7A11 knockdown inhibits melanogenesis-related genes expression in rabbit skin fibroblasts - Naisu Yang; Lin Mu; Bohao Zhao; Manman Wang; Shuaishuai Hu; Bin Zhao; Yang Chen; Xinsheng Wu (Journal of Genetics, 2018)

Turbulent mixing above the Atlantic Water around the Chukchi Borderland in 2014 - Wenli Zhong; Guijun Guo; Jinping Zhao; Tao Li; Xiaoyu Wang; Longjiang Mu (Acta Oceanologica Sinica, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Characteristics of nitrogen removal and microbial community in biofilm system via combination of pretreated lignocellulosic carriers and various conventional fillers - Jing Zhao; Lijuan Feng; Jincheng Dai; Guangfeng Yang; Jun Mu (Biodegradation, 2017)

Method for assessing coal-floor water-inrush risk based on the variable-weight model and unascertained measure theory - Qiang Wu; Dekang Zhao; Yang Wang; Jianjun Shen; Wenping Mu; Honglei Liu (Hydrogeology Journal, 2017)

Effects of climate change and human activities on runoff and sediment inputs of the largest freshwater lake in China, Poyang Lake - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Pengfei Li (Hydrological Sciences Journal, 2017)

Effects of check dams on runoff and sediment load in a semi-arid river basin of the Yellow River - Erhui Li; Xingmin Mu; Guangju Zhao; Peng Gao; Wenyi Sun (Stochastic Environmental Research and Risk Assessment, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Human activity and climate variability impacts on sediment discharge and runoff in the Yellow River of China - Yi He; Fei Wang; Xingmin Mu; Lanqin Guo; Peng Gao; Guangju Zhao (Theoretical and Applied Climatology, 2017)

Changes in daily and monthly rainfall in the Middle Yellow River, China - Yi He; Peng Tian; Xingmin Mu; Peng Gao; Guangju Zhao; Fei Wang; Pengfei Li (Theoretical and Applied Climatology, 2017)

Desulfurization with Thialkalivibrio versutus immobilized on magnetic nanoparticles modified with 3-aminopropyltriethoxysilane - Tingzhen Mu; Jixiang Zhao; Yueping Guan; Jiangnan Tian; Maohua Yang; Chen Guo; Jianmin Xing (Biotechnology Letters, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Chloride Co-transporter NKCC1 Inhibitor Bumetanide Enhances Neurogenesis and Behavioral Recovery in Rats After Experimental Stroke - Wangshu Xu; Xiaopeng Mu; Huibin Wang; Chengguang Song; Wenping Ma; Jukka Jolkkonen; Chuansheng Zhao (Molecular Neurobiology, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Improvement of desulfurizing activity of haloalkaliphilic Thialkalivibrio versutus SOB306 with the expression of Vitreoscilla hemoglobin gene - Tingzhen Mu; Maohua Yang; Jixiang Zhao; Moustafa Mohammed Sharshar; Jiangnan Tian; Jianmin Xing (Biotechnology Letters, 2017)

Erratum to: Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Remote sensing Penman–Monteith model to estimate catchment evapotranspiration considering the vegetation diversity - Fawen Li; Runxiang Cao; Yong Zhao; Dongjing Mu; Changfeng Fu; Feng Ping (Theoretical and Applied Climatology, 2017)

Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Regime shift of the dominant factor for halocline depth in the Canada Basin during 1990–2008 - Longjiang Mu; Jinping Zhao; Wenli Zhong (Acta Oceanologica Sinica, 2017)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Effective degradation of rhodamine B by electro-Fenton process, using ferromagnetic nanoparticles loaded on modified graphite felt electrode as reusable catalyst: in neutral pH condition and without external aeration - Jiangnan Tian; Jixiang Zhao; Ayobami Matthew Olajuyin; Moustafa Mohamed Sharshar; Tingzhen Mu; Maohua Yang; Jianmin Xing (Environmental Science and Pollution Research, 2016)

Meandering channel sandstone architecture characterization based on architecture seismic forward simulation - Hongwei Liang; Longxin Mu; Zifei Fan; Lun Zhao; Xiaoqing Zhao; Liangdong Zhao (Arabian Journal of Geosciences, 2016)

One new cycloartane triterpene glycoside from Beesia calthaefolia - Jin-Yuan Zhao; Li-Hua Mu; Xian-zhe Dong; Yuan Hu; Ping Liu (Natural Product Research, 2016)

Sublethal concentration of benzothiazole adversely affect development, reproduction and longevity of Bradysia odoriphaga (Diptera: Sciaridae) - Yunhe Zhao; Peng Zhang; Yongbiao Zhai; Chengyu Chen; Qiuhong Wang; Jingkun Han; Zhengqun Zhang; Feng Liu; Wei Mu (Phytoparasitica, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Fluazinam Residue and Dissipation in Potato Tubers and Vines, and in Field Soil - Xiaoxiao Feng; Kai Wang; Zhaobin Mu; Yuzhen Zhao; Hongyan Zhang (American Journal of Potato Research, 2015)

Changing trends and regime shift of streamflow in the Yellow River basin - Guangju Zhao; Erhui Li; Xingmin Mu; Zhongming Wen; Scott Rayburg; Peng Tian (Stochastic Environmental Research and Risk Assessment, 2015)

Water use efficiency of net primary production in global terrestrial ecosystems - Lei Xia; Fei Wang; Xingmin Mu; Kai Jin; Wenyi Sun; Peng Gao; Guangju Zhao (Journal of Earth System Science, 2015)

Enriched Environment Altered Aberrant Hippocampal Neurogenesis and Improved Long-Term Consequences After Temporal Lobe Epilepsy in Adult Rats - Xiaoqian Zhang; Tingting Liu; Zhike Zhou; Xiaopeng Mu; Chengguang Song; Ting Xiao; Mei Zhao; Chuansheng Zhao (Journal of Molecular Neuroscience, 2015)

Regional characteristics of sea ice thickness in Canadian shelf and Arctic Archipelago measured by Ground Penetrating Radar - Tao Li; Jinping Zhao; Yutian Jiao; Jiaqiang Hou; Longjiang Mu (Acta Oceanologica Sinica, 2015)

Wet deposition flux and runoff output flux of mercury in a typical small agricultural watershed in Three Gorges Reservoir areas - Zheng Zhao; Dingyong Wang; Ya Wang; Zhijian Mu; Jinshan Zhu (Environmental Science and Pollution Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Cloning and expression pattern of akirin2 gene in broiler - Chaolai Man; Yang Chang; Weitao Mu; Dongxue Zhao (Molecular and Cellular Biochemistry, 2014)

A novel microbead-based microfluidic device for rapid bacterial identification and antibiotic susceptibility testing - J. He; X. Mu; Z. Guo; H. Hao; C. Zhang; Z. Zhao; Q. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Attribution of maize yield increase in China to climate change and technological advancement between 1980 and 2010 - Jianping Guo; Junfang Zhao; Dingrong Wu; Jia Mu; Yanhong Xu (Journal of Meteorological Research, 2014)

Bioremediation of endosulfan in laboratory-scale constructed wetlands: effect of bioaugmentation and biostimulation - Congcong Zhao; HuiJun Xie; Yang Mu; Xiaoli Xu; Jian Zhang; Cui Liu; Shuang Liang; Huu Hao Ngo; Wenshan Guo; Jingtao Xu; Qian Wang (Environmental Science and Pollution Research, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Cycloartane-type triterpene glycosides from Beesia calthaefolia and their anticomplement activity - Li-Hua Mu; Hong-Jie Li; Dai-Hong Guo; Jin-Yuan Zhao; Ping Liu (Journal of Natural Medicines, 2014)

Scenario analysis on the adaptation of different maize varieties to future climate change in Northeast China - Yanhong Xu; Jianping Guo; Junfang Zhao; Jia Mu (Journal of Meteorological Research, 2014)

Functions of the nicotinamide adenine dinucleotide phosphate oxidase family in G anoderma lucidum : an essential role in ganoderic acid biosynthesis regulation, hyphal branching, fruiting body development, and oxidative‐stress resistance - Dashuai Mu; Chenyang Li; Xuchen Zhang; Xiongbiao Li; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2014)
Summary G anoderma lucidum has drawn worldwide interest with regard to its secondary metabolism and pharmaceutical activity. However, the development of such research has been limited because of a lack of basic biological knowledge. Nicotinamide adenine dinucleotide phosphate oxidases (Nox) have recently been highlighted because of the many important biological roles in plants and animals; however, the exact functions of Nox are still not fully understood in fungi. In this study, we identified two N ox isoforms ( NoxA and NoxB ) and a regulator, NoxR . RNA interference was used, and silencing of the Nox isoforms and NoxR expression indicated a central role for these genes in hyphal branching, fruiting body development, reactive oxygen species ( ROS ) generation, ROS resistance and ganoderic acid biosynthesis regulation. Further mechanistic investigation revealed that N ox‐generated ROS elevated cytosolic Ca 2+ levels by activating a plasma membrane Ca 2+ influx pathway, thereby inducing the Ca 2+ signal pathway to regulate ganoderic acid biosynthesis and hyphal branching. Importantly, our results highlight the N ox functions in signal crosstalk between ROS and Ca 2+ , and these findings provide an excellent opportunity to identify the potential pathway linking ROS networks to calcium signalling in fungi and suggest that plants, animals and fungi share a conserved signal‐crosstalk mechanism.

Metal Pollution (Cd, Pb, Zn, and As) in Agricultural Soils and Soybean, Glycine max, in Southern China - Yunyun Zhao; Xiaolong Fang; Yinghui Mu; Yanbo Cheng; Qibin Ma; Hai Nian; Cunyi Yang (Bulletin of Environmental Contamination and Toxicology, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Molecular cloning and expression of a C-type lectin gene from Venerupis philippinarum - Changkao Mu; Leilei Chen; Jianmin Zhao; Chunlin Wang (Molecular Biology Reports, 2014)

Global detection of large lunar craters based on the CE-1 digital elevation model - Lei Luo; Lingli Mu; Xinyuan Wang; Chao Li; Wei Ji; Jinjin Zhao; Heng Cai (Frontiers of Earth Science, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

MicroRNA-153 is tumor suppressive in glioblastoma stem cells - Shiguang Zhao; Yifan Deng; Yaohua Liu; Xin Chen; Guang Yang; Yulong Mu; Daming Zhang; Jianhao Kang; Zhaoli Wu (Molecular Biology Reports, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Indoor air pollution and risk of lung cancer among Chinese female non-smokers - Lina Mu; Li Liu; Rungui Niu; Baoxing Zhao; Jianping Shi; Yanli Li; Mya Swanson; William Scheider; Jia Su; Shen-Chih Chang; Shunzhang Yu; Zuo-Feng Zhang (Cancer Causes & Control, 2013)

Integrin β8 Signaling in Neonatal Hypoxic–Ischemic Brain Injury - Li Zhang; Yi Qu; Binzhi Tang; Fengyan Zhao; Tao Xiong; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2012)

Phylogeny of Celastrus L. (Celastraceae) inferred from two nuclear and three plastid markers - Xian-Yun Mu; Liang-Cheng Zhao; Zhi-Xiang Zhang (Journal of Plant Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Molybdenum improves antioxidant and osmotic-adjustment ability against salt stress in Chinese cabbage (Brassica campestris L. ssp. Pekinensis) - Mu Zhang; Chengxiao Hu; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Anyong Cao; Min Cui; Ying Zhang (Plant and Soil, 2012)

Molecular cloning, characterization, and function analysis of a mevalonate pyrophosphate decarboxylase gene from Ganoderma lucidum - Liang Shi; Lei Qin; Yingjie Xu; Ang Ren; Xing Fang; Dashuai Mu; Qi Tan; Mingwen Zhao (Molecular Biology Reports, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Activation of glycine site and GluN2B subunit of NMDA receptors is necessary for ERK/CREB signaling cascade in rostral anterior cingulate cortex in rats: Implications for affective pain - Hong Cao; Wen-Hua Ren; Mu-Ye Zhu; Zhi-Qi Zhao; Yu-Qiu Zhang (Neuroscience Bulletin, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)

A comparison of different optimization algorithms for retrieving aerosol optical depths from satellite data: an example of using a dual-angle algorithm - Xihan Mu; Qingfeng Shen; Zhao-Liang Li; Guangjian Yan; José Antonio Sobrino (International Journal of Remote Sensing, 2011)

MiR-106a inhibits glioma cell growth by targeting E2F1 independent of p53 status - Guang Yang; Ruyou Zhang; Xiaofeng Chen; Yulong Mu; Jing Ai; Chen Shi; Yaohua Liu; Changbin Shi; Lihua Sun; Nikolai G. Rainov; Hulun Li; Baofeng Yang; et al. (Journal of Molecular Medicine, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Comparative Life Cycle Assessment of Lignocellulosic Ethanol Production: Biochemical Versus Thermochemical Conversion - Dongyan Mu; Thomas Seager; P. Suresh Rao; Fu Zhao (Environmental Management, 2010)

Efficiency of methods applied for goat estrous synchronization in subtropical monsoonal climate zone of Southwest China - Yongju Zhao; Jiahua Zhang; Hong Wei; Xinming Sun; Biao Mu; Mingju Yu; Lingbing Wang (Tropical Animal Health and Production, 2010)

The Role of Integrin αvβ8 in Neonatal Hypoxic-Ischemic Brain Injury - Jinhui Li; Yi Qu; Xihong Li; Deyuan Li; Fengyan Zhao; Meng Mao; Donna Ferriero; Dezhi Mu (Neurotoxicity Research, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

A strategy to integrate a priori knowledge for an improved inversion of the LAI from BRDF modelling - Guangjian Yan; Xihan Mu; Yinchi Ma; Zhao‐Liang Li (International Journal of Remote Sensing, 2008)

Uncertainty and sensitivity ratio of parameters in estimating and promoting retrieval accuracy - Xihan Mu; Guangjian Yan; Zhao‐Liang Li (International Journal of Remote Sensing, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Antifungal agent and other constituents from Cynanchum otophyllum - Yi-Bin Zhao; Yue-Mao Shen; Hong-Ping He; Quan-Zhang Mu; Xiao-Jiang Hao (Natural Product Research, 2007)

Effect of sensitivity to abscisic acid on scaling relationships for biomass production rates and body size in Arabidopsis thaliana - Hao Zhang; Gen-Xuan Wang; Zhu-Xia Shen; Xing-Zheng Zhao; Mu-Qing Qiu (Acta Physiologiae Plantarum, 2006)

Impact of elevated CO2 concentration under three soil water levels on growth of Cinnamomum camphora - Xing-zheng Zhao; Gen-xuan Wang; Zhu-xia Shen; Hao Zhang; Mu-qing Qiu (Journal of Zhejiang University-SCIENCE B, 2006)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

A GIS-based research on the distribution of rural settlements in Yulin of northern Shaanxi - Zhao Mu-dan; Tang Guo-an; Shi Wen-zhong; Liu Yong-mei (Journal of Geographical Sciences, 2002)

Evaluation on the accuracy of digital elevation models - Tang Guo-an; Josef Strobl; Gong Jian-ya; Zhao Mu-dan; Chen Zhen-jiang (Journal of Geographical Sciences, 2001)